Evaluating the Influence of Landscape Structure on PM2.5 Variability: A Geospatial-remote Sensing Big Data Perspective - Asghary Mohammed Ismail; Rizwan Muhammad (International Journal of Environmental Research, 2026)

Gellan gum as a versatile biopolymer: A 20-year bibliometric review with emerging insights into probiotic delivery - Zaleha Mahmod; Muhammad Faiz Zulkifli; Wan Iryani Wan Ismail; Mohd Ariff Sharifudin; Mohd Hafiz Bin Arzmi; Khairul Anuar Mat Amin (Bioactive Carbohydrates and Dietary Fibre, 2026)

Honeybee venom modulates antioxidant gene expression and tissue regeneration in a rat model of staphylococcus aureus - infected skin wounds - Sabir Ahmed Smael; Treefa Farouq Ismail; Banaz Sdiq Abdullah; Rebwar Muhammad Hamasalih; Esmat Khaleqsefat; Azheen Subhi Abdulrahman; Ramyar Hassan Mahmud; Abubakr Mohammed Amin; Rozi Braim Abdalrahman; Harem Khdir Awla (Molecular Biology Reports, 2026)

Inhibition of SARS-CoV-2 spike S1–ACE2 binding interaction and downregulation of ACE2 gene expression by Malaysian stingless bee honey and its bioactive compound, stilbamidine (SDC) - Che Muhammad Khairul Hisyam Ismail; Azlini Ismail; Mohd Ridzuan Mohd Abd Razak; Azzmer Azzar Abdul Hamid; Khairani Idah Mokhtar; Widya Lestari; Basma Ezzat Mustafa Alahmad (Molecular Biology Reports, 2026)

Correction: Molecular characterization and cuticular stomatal anatomy of Punica Granatum L. cultivars study in Dohuk governorate - Dalal Y. Kh. Sinjare; Shamiran S. Abdulrahman; Nizek S. Khalid; Rizgar Y. Ismail; Muhammad Yasir Naeem; Zeliha Selamoglu; Gani Issayev; Aveen M. N. Ahmed (Molecular Biology Reports, 2026)

Suppression of microRNAs targeting key MEP pathway genes affects plastid terpenoid content and photosynthesis under variable light conditions - Syed Muhammad Iqbal Syed Othman; Arif Faisal Mustaffa; Muhammad Sajad; Muhamad Hafiz Che-Othman; Hoe-Han Goh; Ismanizan Ismail (Molecular Biology Reports, 2026)

Suppression of miR426 enhances photoprotection and chlorophyll stability via upregulation of ELIP2 in Arabidopsis thaliana - Arif Faisal Mustaffa; Syed Muhammad Iqbal Syed Othman; Nur Irdina Izzatie Mohd Zahid; M. Hafiz Che-Othman; Hoe-Han Goh; Muhammad Sajad; Ismanizan Ismail (Molecular Biology Reports, 2026)

Transgene-free plant genome editing via viral delivery of miniature CRISPR-Cas12f - Muhammad Jawad Akbar Awan; Afzal Akram; Rubab Zahra Naqvi; Mariam Akhtar; Saqib Siddique; Muhammad Ismail Buzdar; Imran Amin; Shahid Mansoor (Functional & Integrative Genomics, 2026)

Integrated gravity and landsat analyses for hydrothermal alteration and fault zone mapping in the lokop geothermal prospect, Indonesia - Faisal Abdullah; Muhammad Yanis; Muhammad Ridha Adhari; Dian Darisma; Gartika Satria Nugraha; Muzakir Zainal; Nazli Ismail (Earth Science Informatics, 2026)

Electrospun polyacrylonitrile nanofiber membrane incorporating palm kernel shell activated carbon and tin for wastewater filtration: Characterization and permeability optimization - Rahma Dani; Agung Mataram; Ahmad Fauzi Ismail; Muhammad Satya Putra Gantada; Raisha Syafira Ap Idjan; Muhammad Rama Almafie; Leni Marlina; Ida Sriyanti (Journal of Water Process Engineering, 2026)

Nanoplastic removal from water using metal–organic framework-based adsorbents and membrane systems: Mechanisms, performance, and practical perspectives - Muhammad Fahad Tariq; I. Ihsanullah; Farhan Javed; Ismail W. Almanassra; Muataz Ali Atieh (Journal of Water Process Engineering, 2026)

Effect of low-temperature treatment on the physicochemical, interfacial, and foaming properties of wheat gliadin nanoparticles - Muhammad Asif Ismail; Tianxu Liu; Ying Jiang; Abel Wend-Soo Zongo; Mohamed Eid; Jing Li; Bin Li (Food Chemistry, 2026)

Fabrication of multifunctional biomaterial through conjugation between whey protein isolate and punicalagin - Mahmoud Youssef; Essam Hady; Fayez Khalaf Mourad; Muhammad Asif Ismail; Chenguang Yao; Hongshan Liang; Bin Li (Food Chemistry, 2026)

A novel hybrid cooling strategy for residential buildings integrating PV-powered AC and PCM thermal energy storage with intermittent operation - Zeyad Amin Al-Absi; Muhammad Asif; Ismail M. Budaiwi; Mohammed Alhaji Mohammed; Nedhal Al-Tamimi (Energy and Buildings, 2026)

Nutrient Enrichment Patterns and Spatial Heterogeneity in Enne Dam Lake (Sakarya River Watershed, Türkiye): Insights for Watershed Management Strategies - Cem Tokatlı; Said Muhammad; Alper Uğurluoğlu; Ahmet Bahtiyar Arvas; Rahmatullah Hakımı; İlker Manav; İsmail Yoşumaz; Caner Dilber (Water, Air, & Soil Pollution, 2026)

Defect-engineered MIL-100(Fe) via acid modulation for enhanced adsorption and selectivity in dye removal from wastewater - Mohd Amir Asyraf Mohd Hamzah; Muhammad Ahnaf Mohd Azmi; Rickson Jun Jay Chia; Norhaniza Yusof; Woei Jye Lau; Ahmad Fauzi Ismail; Hasrinah Hasbullah (Journal of Water Process Engineering, 2026)

Reversible -NH2/-NH3+ switching drives proton-coupled electron transfer for selective CO2-to-CO photoreduction in S-scheme MOF/g-C3N4 heterojunction - Sharafat Ali; Sher Ali; Ahmed Ismail; Yong Wang; Syed Ul Hasnain Bakhtiar; Qaisar Alam; Pir Muhammad Ismail; Wajid Ali; Ahmad Iqbal; Polycarpos Falaras; Jiabao Yi; Fazal Raziq; et al. (Chemical Engineering Journal, 2026)

Impact of Land Use Change on Water Quality: Toward Sustainable Ecosystem Management in the Nenggiri River Basin - Ismafatin Nabilah Ismail; Mohd Khairul Amri Kamarudin; Mohamad Hafis Amat Simin; Asmawi Ibrahim; Wan Nor Azilawanie Tun Ismail; Ahmad Shakir Mohd Saudi; Mohd Ekhwan Toriman; Sunardi Sunardi; Firdaus Muhammad-Sukki (Water, Air, & Soil Pollution, 2026)

Large-scale microtremor analysis and lineament mapping for evaluating geological hazards in reservoir-induced seismicity regions: The case history of Kenyir Geopark - Susie Cahyanti Tasman; Neeran Niraj; Muhammad Noor Hisyam Jusoh; Abdul Halim Abdul Latiff; Siti Nur Fathiyah Jamaludin; Muhd Nur Ismail Abdul Rahman; Rudiyanto; Muhammad Afiq Md Ali; Muhamad Zaki Zulkifli; Yuzwan Mohamad; Kee Soo Chen; Fawwaz Azfar Abd Ghafar; et al. (Journal of Applied Geophysics, 2026)

Digital twin-centered food safety management systems: A review of IoT, AI, and blockchain integration for bacterial pathogen control - Balarabe B. Ismail; Abdulrazaq Hassan Abba; Abdulrashid Ibrahim Sanka; Aliyu Idris Muhammad; Wenjun Wang; Donghong Liu (Food Research International, 2026)

Complementary effects of silicon-induced plant defense and Trichogramma pretiosum biological control of fall armyworm in maize - Kamran Haider; Muhammad Sufian; Dilawar Abbas; Kamil Kabir; Muhammad Lubaid Khalid; Ahmed Mahmoud Ismail (Journal of Plant Diseases and Protection, 2026)

Impacts of infrastructure development on taxonomic and functional diversity of non-volant small mammals - Ummi Nur Syafiqah Daud; Muhammad Iqbal Md. Jamaluddin; Nor Adibah Ismail; Nurfatin Batrisyia Md. Ali; Noor Fatihah Najihah Arazmi; Norfazliyana Nordin; Saiful Hilmi Jamal Shuhaily; Fudzla Zulfa Khiruddin; Amirul Haikal Zainal; Shukor Md. Nor; Aisah Shukor; Mohammad Saiful Mansor (Biodiversity and Conservation, 2026)

Effect of Equivalence Ratio in a Waste Oil Burner on Performance and Emission Characteristics Fuelled with Sludge Palm Oil Blends - Muhammad Ahmar Zuber; Wira Jazair Yahya; Sonachalam Muthuswamy; Ili Fatimah Abd Razak; Mohamed Shukri Mohamed Ismail; Hirofumi Noge (Emission Control Science and Technology, 2026)

Design of a multi-epitope vaccine candidate against Mycobacterium ulcerans for the prevention of Buruli ulcer - Muhammad Asim; Ramy S. Yehia; Hotaf Hassan Makki; Ahmed M. Ismail (Biologia, 2026)

Ecotoxicological and health risk assessing of heavy metals and microplastics in African catfish (Clarias gariepinus) of Burullus Lake, Egypt - Muhammad A. El-Alfy; Marwa M. AbouHadied; Tahany A. Ismail (Environmental Science and Pollution Research, 2026)

Exploiting the biocontrol potential of Chaetomium globosum against Fusarium solani root rot in wheat: climate-responsive phytohormonal regulation, genetic diversity, and sustainable management - Marwa S. Fouad; Khaled M. A. Ramadan; Hisham A. Mohamed; Mohamed Abou-Zeid; Shafik D. Ibrahim; Muhammad Munir; Eslam S. A. Bendary; Mohamed M. Aboul Fotouh; Sallah A. Al Hashedi; Adil AlShoaibi; Zafar Iqbal; Ahmed M. Ismail; et al. (European Journal of Plant Pathology, 2026)

Provenance, tectonic settings, depositional conditions, and diagenetic features of the late Cretaceous (Coniacian–Santonian) Fika Shale, Upper Benue Trough, Northeastern Nigeria: Implications for hydrocarbon potential - Abdulwahab Bello; Musa B. Usman; Shehu Mukkafa; Ibrahim A. Kwami; Usman Abubakar; Abduljamiu O. Amao; Anas M. Salisu; Khalid Al-Ramadan; Muhammad A. Ismail; Abubakar S. Maigari; Ahmed I. Haruna; Bandar D. Al-Otaibi; et al. (Journal of African Earth Sciences, 2026)

Assessing reach and perceptions of hygiene behaviour change interventions for people with disabilities and older adults: Multi-country matched cross-sectional study - Kazy Farhat Tabassum; Dewan Muhammad Shoaib; Md. Assaduzzaman Rahat; Mehedi Hasan; Dani Barrington; Ben Tidwell; Lauren D'Mello-Guyett; Anjali Sharma; Sheillah Simiyu; Ismail Hosen; Jenala Chipungu; Fachruddin Mangunjaya; et al. (International Journal of Hygiene and Environmental Health, 2026)

The emerging and escalating consequences of rural depopulation in the Himalaya - Karuna Budhathoki; Bhola Bhattarai; Bed Mani Dahal; Shalini Dhyani; Ambika P. Gautam; Binita Guragain; Dibya Devi Gurung; Muhammad Ismail; Om Katel; Sarala Khaling; Kristina Marquardt; Ulrike Müller-Böker; et al. (Global Environmental Change, 2026)

Functional and structural characterization of the SARS-CoV-2 spike N481K mutation - Maria K. Smatti; Hebah Al-Khatib; Muhammad Suleman; Muna Nizar; Hala Abo Khalid; Ruaa Ismail; Gheyath K. Nasrallah; Hadi M. Yassine (Archives of Virology, 2026)
Background: Selective pressure drives SARS-CoV-2 evolution, with spike RBD substitutions shaping ACE2 binding and antibody escape. N481K RBD mutation emerged early in Qatar (2020) and later re-emerged globally, reaching near-fixation by 2024–2025, yet its functional significance remained unexplored. Methods: We analyzed the temporal and geographic circulation of N481K across > 17 million SARS-CoV-2 genomes (2020–2025). Structural effects were assessed using modeling, docking, and molecular dynamics. Functional impact was evaluated using VSV pseudovirus neutralization tests with sera from infected individuals (n = 48) and vaccinated cohorts: mRNA (n = 16), Sinopharm (n = 45), and AstraZeneca (n = 28). Results: N481K was detected in 4.14% (703,777/17,016,111) of global genomes and reached near-fixation (> 90%) in dominant Omicron lineages by 2024, with prevalence rising from 71.5% in early 2024 to 94.4% by week 36 of 2025. Structural analyses showed a 0.706 Å RMSD deviation and higher ACE2 docking affinity (–313 vs. − 308 kcal/mol) compared to the wild-type (WT) RBD. Molecular dynamics confirmed increased stability and lower binding free energy for N481K versus WT (–77.07 ± 0.90 vs. − 43.09 ± 0.98 kcal/mol). Among samples with detectable WT neutralization (n = 89), mean neutralization declined from 69.76% (WT) to 42.47% (N481K) (p

Beyond UV: Overcoming the Optical Bottleneck in Photodesulfurization of Diesel Oil Via Visible and Red-light Harvesting - Dino Dewantara; Ismail Ismail; Ambo Intang; Fatur Assyidiq; Ananda Aprilia; Selpiana Selpiana; Muhammad Djoni Bustan; Sri Haryati (Journal of Fluorescence, 2026)

Dual-template structure-based design of novel harmine derivatives as EGFR inhibitors for colorectal cancer therapy - Sagir Yusuf Ismail; Murtala Muhammad; Tasiu Abdulmumin Mikail; Zakari Nuhu Lambu; Bishir Usman (In Silico Pharmacology, 2026)

β-radiation exfoliation of LDH nanosheets for next-generation water treatment membranes - Muhammad ‘Adli Nor Azman; Pei Sean Goh; S. Selambakkannu; Yuyang Yao; Ahmad Fauzi Ismail; Khairulnadzmi Jamaluddin; Nur Diyana Suzaimi; Ahmad Syazwan Sahril (Journal of Environmental Chemical Engineering, 2026)

A novel varying component gaussian mixture model for improved drought assessment based on standardized-type drought indices - Muhammad Ismail; Muhammad Mohsin (Theoretical and Applied Climatology, 2026)

Biochemical Characterization and Phylogenetic Diversity Assessment of Onion (Allium Cepa L.) Genotypes - Samira Habib; Syed Dilnawaz Ahmad Gardezi; Ahmed Mahmoud Ismail; Safira Attacha; Sajid Fiaz; Muhammad Imran Hamza; Armghan Shehzad; Shazia Arif (Plant Molecular Biology Reporter, 2026)

Development and Optimization of a Fixed Dose Combination Tablet Containing Ibuprofen and Loratadine Using Design Expert and Box-Behnken Design - Muhammad Faheem; Lateef Ahmad; Umar Farooq; Kiramat Ali Shah; Ismail Khan; Abdur Rauf; Omar S. Bahattab; Yahya S. Al-Awthan; Anees Ahmed Khalil; Huda Ateeq (Journal of Pharmaceutical Innovation, 2026)

Mapping of buried archaeological ruins using magnetic and gravity methods around the 17th-century fort of Gunong Biram, Aceh Besar, Indonesia - Amir Asyqari; Nazli Ismail; Muhammad Nanda; Tomi Afrizal; Muhammad Yanis; Deni Sutrisna; Repelita Wahyu Oetomo; Cut Dewi (Geosciences Journal, 2026)

Naproxen as an emerging environmental contaminant: Microbial degradation mechanism and optimization strategies - Irdeana Marsha Baharuddin; Siti Khadijah Awang; Muhammad Iqbal Mashudi; Wan Iryani Wan Ismail; Fazilah Ariffin (Biodegradation, 2026)

Environmetric-driven health risk assessment of indoor air quality and sick building syndrome in educational facilities through integrated pattern recognition and spatial epidemiology - Syazwan Aizat Ismail; Haslinda Mohamed Kamar; Nazri Kamsah; Nur Azzalia Kamaruzaman; Muhammad Iftishah Ramdan; Björn Crüts; Muaz Mohd Zaini Makhtar; Mohd Rafatullah; Aseem Vashisht (Air Quality, Atmosphere & Health, 2026)

NMR-based metabolomics of Indonesian jamu for diabetes: chemical composition, toxicity, and zebrafish behavioral impact - Muhammad Safwan Ahamad Bustamam; Wimbuh Tri Widodo; Mohd Zuwairi Saiman; Siti Munirah Mohd. Faudzi; Siok Geok Chong; Nur Diana Safura Mohd Ezmir; Emelia Asmara Md Daud; Sonny Kristianto; Intan Safinar Ismail (Natural Product Research, 2026)

Corrigendum to “Predicting blue carbon sequestration in Sundarban coastal mangroves: A spatially explicit approach with INVEST and machine learning to advance climate resilience and UN SDG-aligned nature-based climate solutions” [Mar. Pollut. Bull. 226 (2026) 119387] - Ismail Mondal; SK Ariful Hossain; Muhammad Tauhidur Rahman; Wafeek Mohamed Ibrahim; Mukhiddin Juliev (Marine Pollution Bulletin, 2026)

Predicting blue carbon sequestration in Sundarban coastal mangroves: A spatially explicit approach with INVEST and machine learning to advance climate resilience and UN SDG-aligned nature-based climate solutions - Ismail Mondal; SK Ariful Hossain; Muhammad Tauhidur Rahman; Wafeek Mohamed Ibrahim; Mukhiddin Juliev (Marine Pollution Bulletin, 2026)

Where waters transform: Hydrographic variability and turbulent mixing in the lifamatola passage, Indonesia - Adi Purwandana; Zheng Wang; Rui Li; Zhenhua Xu; Yao Li; Dewi Surinati; Fuad Azminuddin; Bayu Priyono; Dwiyoga Nugroho; Muhammad R. Cordova; Teguh Agustiadi; Mochamad R. Iskandar; et al. (Progress in Oceanography, 2026)

Unraveling internal concentration polarization of forward osmosis membrane through β-radiation-exfoliated LDH for heavy metal ion removal - Muhammad 'Adli Nor Azman; Pei Sean Goh; Takaaki Taniguchi; S. Selambakkannu; Yuyang Yao; Ahmad Fauzi Ismail; Khairulnadzmi Jamaluddin; Rendy Muhamad Iqbal (Journal of Water Process Engineering, 2026)

Modulating the thermo-immuno-endocrine axis to alleviate heat stress in poultry: A pharmacological perspective - Mohamed E. Abd El-Hack; Ahmed I. Elsherbeni; Amira K. Hajri; Marzough A. Albalawi; Mohamed AbdElrahman; Mahmoud Moustafa; Mohammed Al-Shehri; Muhammad Asif Arain; Ismail E. Ismail (Journal of Thermal Biology, 2026)

Unveiling Morpho-Anatomical Strategies of Cenchrus Ciliaris L. for Survival under Vehicular Pollution Stress - Hafiz Muhammad Mohsin Hassan; Muhammad Akram; Imran Haider; Muhammad Altaf Nazir; Lamy Hamed; Abdullateef Al-Saeed; ElSayed A. Badr; Ahmed Ismail (Water, Air, & Soil Pollution, 2026)

Myricetin as a potential therapeutic agent against Pseudomonas aeruginosa : inhibition of biofilm formation, quorum sensing, and virulence factor production - Sallah A. Al Hashedi; Saif M. Dmour; Hamad Sarheed Galut; Ayman Daifallah Ismail Alsheikh; Mohammad H. Abukhalil; Sham Ma’aitah; Najeeb S. Al-Zoreky; Khaled M.A. Ramadan; Muhammad Naeem Sattar; Zafar Iqbal; Adil Alshoaibi; Sultan A. M. Saghir (Biofouling, 2026)

A review of floating renewable energy technologies for sustainable development - Mir Murtaza Zangejo; Muhammad Ismail Jamali; Mohsin Ali Koondhar; Abdul Sattar Saand; Ibrahim Mahariq; Ezzeddine Touti (Ocean Engineering, 2026)

Individual and combined decontamination effect of aqueous ozone and plant extracts on fungi and aflatoxins in brown rice - Iqra Naeem; Amir Ismail; Yun Yun Gong; Muhammad Riaz; Muhammad Arif Shahzad; Aneela Hameed; Mubashir Aziz; Asif Mahmood; Waheed Al Masry; Muhammad Latif; Sher Ali; Carlos A.F. Oliveira (Food Control, 2026)

Bacteriophage-Based Vaccine Platform for Next Generation Vaccine Development Against Bovine Tuberculosis and Other Pulmonary Diseases of Animals - Shahzar Khan; Nadia Ilyas; Fida Ullah Khan; Aneela Nawaz; Mohammed Raashid; Muhammad Ismail Khan; Momina Aamir; Aamer Ali Shah; Malik Badshah; Brekhna Alam; Samiullah Khan (International Journal of Peptide Research and Therapeutics, 2026)

Hydrothermal synthesis of novel Mn3O4-Nd2O4 nano-hybrid as bi-functional electrocatalyst for water splitting - Muhammad Ibrar; Iram Manzoor; Mostafa A. Ismail; Misbah Shareef; Habiba Batool; Sana Ben Khalifa; Saleh Chebaane; Zeineb Klai (Fuel, 2026)

Technological trends in rainwater harvesting for micro-hydropower: a scientometric review - S. N. F. Abdullah; M. K. A. Kamarudin; N. A. Wahab; N. Yaakub; A. S. Mohd Saudi; M. N. A. Rahman; S. Sunardi; F. Muhammad-Sukki; I. N. Ismail (International Journal of Energy and Water Resources, 2026)

Genomic characterization of Burkholderia glumae K6 and B. gladioli UPMBG7: causal agents of bacterial panicle blight in Malaysia - Adam Zafdri Md Zali; Siti Izera Ismail; Norsazilawati Saad; Muhammad Asyraf Md Hatta; Mohd Razi Ismail; Mohd Termizi Yusof; Mansor Hakiman; Syari Jamian; Sumaiyah Abdullah; Dzarifah Zulperi (European Journal of Plant Pathology, 2026)
Bacterial panicle blight (BPB), caused by Burkholderia glumae and B. gladioli , is a major threat to rice in Malaysia, with potential yield losses up to 75%. In June 2021, BPB symptoms were detected in Kedah rice fields. Isolates were identified through phenotypic traits, pathogenicity tests, and molecular analysis (16S rRNA and gyrB sequencing). Whole-genome sequencing of B. glumae K6 and B. gladioli UPMBG7 was performed using the Illumina NovaSeq 6000 platform. The assembled draft genome of B. glumae K6 contained 210 contigs, with a total genome size of 6.57 Mbp, 68.33% G + C content, and 5,641 coding sequences (CDS). It harbored toxoflavin biosynthesis genes ( toxABCDE , toxJ ) and a Type III secretion system (T3SS), contributing to its pathogenicity. B. gladioli UPMBG7 contained 124 contigs, with a total genome size of 8.22 Mbp, G + C content of 67.99, and 7,022 coding proteins. B. gladioli lacked the toxI gene for toxoflavin production but compensated with pyoverdine siderophore genes ( pvdA ), which facilitate iron acquisition. These findings highlight divergent infection mechanisms, with B. glumae relying on toxoflavin-mediated virulence and B. gladioli on resource competition. The genomic insights support the development of resistant rice cultivars, biological controls, and molecular diagnostics to improve BPB management in Malaysia.

Characterization of aquifer hydraulics and pumping well yield for supplemental paddy crop irrigation using pumping tests in Perak, Malaysia - Naseem Akhtar; Muhammad Izzuddin Syakir; Syahidah Akmal Muhammad; Aznan Fazli Ismail; Mohamad Shaiful Md. Yusuff; Leila Bouida; Hamza Mohamed Flafel; Pahmi Husain; Mohammed Benaafi; Taskin Ahmed; Mohammad Muqtada Ali Khan (Paddy and Water Environment, 2026)

Advancing future drought characterization: a two-phase Bayesian model averaging approach for GCM ensemble calibration - Nosheen Amjad; Muhammad Ismail; Zulfiqar Ali (Applied Geomatics, 2026)

Development of rare earth metal-supported manganese selenide (MnSe2-Nd2O3) heterostructure enabling robust hydrogen evolution reaction - Muhammad Abdul; Chingmai Ko; Mostafa A. Ismail; Sana Ben Khalifa; Norah A.M. Alsaif; Saleh Chebaane; Jehan Akbar; Suleyman I. Allakhverdiev (Fuel, 2026)

Development of Kling–Gupta Hybrid Weighted Ensemble for Improving Future Projections of Drought Characterization Under Different Climate Change Scenarios - Nosheen Amjad; Muhammad Ismail; Zulfiqar Ali (Pure and Applied Geophysics, 2026)

Water quality and pollution dynamics in the Padma River, Bangladesh: Characterization of microbiological and chemical contaminants - Mohammad Kamruzzaman; Md. Nayeem; Mohammad Ismail; Md Firoz Khan; Sharmin Zaman Emon; Anowar Hosen; Asma Rahman; Muhammad Nurul Huda (Regional Studies in Marine Science, 2026)

Geochemical modeling, evaluation of contaminants and impacts of land use, land cover patterns on groundwater quality in Khushab, Pakistan - Hasnain Abbas; Javed Iqbal; Syed Madhi Haider Kazmi; Maqsood Ahmed; Muhammad Ismail; Wajid Hussain (Journal of Contaminant Hydrology, 2026)

Metal-organic framework-derived defect-enriched bimetallic Cerium/Manganese oxide nanocomposite with carbon for boosted water electrolysis and supercapacitor applications - Tauseef Munawar; Ambreen Bashir; Sonia Sardar; Muhammad Rafaqat; Guo Changqing; Mostafa A. Ismail; Shoukat Alim Khan; Muammer Koc; Suleyman I. Allakhverdiev; Faisal Iqbal; Chang-Feng Yan (Fuel, 2026)

Electron-rich sulfur sites and dual interfacial bonds in S-scheme heterojunction enable high quantum yield and stable hydrogen production - Sharafat Ali; Sajjad Ali; Shu-Long Li; Ahmed Ismail; Sher Ali; Pir Muhammad Ismail; Syed Ul Hasnain Bakhtiar; Fazal Raziq; Mohammad Z. Rahman; Liang Qiao (Chemical Engineering Journal, 2026)

Unravelling the spatiotemporal causality chain between meteorological and agricultural drought propagation in the China–Pakistan Economic Corridor - Muhammad Ismail; Kadambot H.M. Siddique; Yi Li (Atmospheric Research, 2026)

Modelling of electrolyzers and fuel cells for grid services under high RES penetration - Sulaiman S. Ahmad; Abdullah A. Almehizia; Muhammad Khalid; Fahad Saleh Al-Ismail (Next Research, 2025)

Bacteriophage-based vaccination platform for antigen discovery and development of next-generation vaccines - Shahzar Khan; Nadia Ilyas; Aneela Nawaz; Muhammad Ismail Khan; Momina Aamir; Nauman Ahmed Khalid; Aamer Ali Shah; Numan Saleh Zada; Ghulam Shabbir; Malik Badshah; Samiullah Khan (Next Research, 2025)

Sustainable slope stabilization: root-induced stiffness and damping control in sandy soils under cyclic loading - Ismail Shah; Yuan-Jun Jiang; Mehtab Alam; Xia Xin; Muhammad Mudassar Rehman (CATENA, 2025)

Investigating the Effect of Sn and Pt Doping and Co-doping on the Photocatalytic Efficiency of Zirconia for Degradation of Acid Yellow-76 - Mian Hussain Shah; Saima Sadiq; Umar Wahab; Inam Ullah; Sardar Hussain; Nasr Ullah; Safiullah Khan; Zaffar Iqbal; Muhammad Ismail; Aadil Nabi Chishti; Muhammad Sadiq (Water, Air, & Soil Pollution, 2025)

Molecular characterization and cuticular stomatal anatomy of Punica Granatum L. cultivars study in Dohuk governorate - Dalal Y. Kh. Sinjare; Shamiran S. Abdulrahman; Nizek S. Khalid; Rizgar Y. Ismail; Muhammad Yasir Naeem; Zeliha Selamoglu; Gani Issayev; Aveen M. N. Ahmed (Molecular Biology Reports, 2025)

Carbon Nanotubes Improve Quantitative and Qualitative Attributes of Potato (Solanum tuberosum L) Genotypes - Muhammad Ismail; Muhammad Imtiaz; Raham Sher Khan; Fazal Jalal; Fazal Said; Muhammad Ali Khan; Syed Hussain; Badshah Islam; Salman Khan; Sabir Khan; Atta Ullah; Maqsood Khan; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Integrating hematological profile and biomarker analysis for metals and metalloids ecotoxicological assessment on Wallago catfish and Indian carp health in Head Siphon, Mailsi, Pakistan - Kaynat Saeed; Sajid Abdullah; Muhammad Yaqoob; Minahal Fatima; Zunaira Majeed; Muhammad Ismail; Sara F. Ghanem; Moaheda E.H. Eissa; Hesham Hassanien; Zulhisyam Abdul Kari; El-Sayed Hemdan Eissa (BioMetals, 2025)

Advances in bacterial chromium biosorption: current perspectives and future directions - Abdullahi Adamu Faggo; Bashar Haruna Gulumbe; Nazeef Idris Usman; Tirmizhi Munkaila Abubakar; Kadai Alhaji Lawan; Musbahu Abdullahi Bagwai; Kabir Hassan Sambo; Muhammad Bello; Mubarak Hassan Ismail; Wada Nafiu (Environmental Science and Pollution Research, 2025)

Characterizing Tropical Cyclone from Altimeter Wind Speed Profile - Nik Raisyha Nurfarain Abdullah; Syarawi M. H. Sharoni; Mohd Nadzri Md Reba; Hwee San Lim; Nurul Najwa Ayob; Ismail Ahmad Abir; Muhammad Zahir Ramli (Marine Geodesy, 2025)

Spatiotemporal heterogeneity of evapotranspiration controlling factors and their trends in Pakistan - Najeebullah Khan; Mohammed Magdy Hamed; Mohd Khairul Idlan Muhammad; Salah ud Din; Zulhilmi Ismail; Shamsuddin Shahid (Acta Geophysica, 2025)
Effective climate change mitigation planning in the water and agriculture sectors necessitates a thorough understanding of trends in potential evapotranspiration (ETp) and its driving factors. This study quantitatively assessed the impact of varying meteorological conditions on ETp across Pakistan. We deciphered the dynamics of recent ETp shifts by analyzing trends in meteorological variables using Princeton Global Meteorological Forcing data (daily maximum and minimum temperatures, wind speed, solar radiation, and relative humidity) at 0.25° resolution. Sobol's sensitivity analysis quantified the influence of each climatic variable on ETp. Nonparametric statistical tests identified trends in ETp and its influencing factors. Our findings reveal wind speed as the most critical element controlling ETp across all seasons in Pakistan, followed by solar radiation and temperature. Daily ETp exhibited increasing trends in the north, west, and east, ranging from 0.05 to 0.4 mm/decade. This rise in ETp can be primarily attributed to increasing temperatures, while other parameters like wind speed and solar radiation remained relatively constant. These results suggest that continued global warming-driven ETp increases may pose significant challenges for Pakistan's water supply and agricultural irrigation systems.

Aspergillus spp and aflatoxins in Pakistani rice: A case study on the decontamination effect of accelerated aging and improved storage practices - Iqra Naeem; Amir Ismail; Yun Yun Gong; Muhammad Riaz; Aneela Hameed; Mubashir Aziz; Asif Mahmood; Waheed Al Masry; Muhammad Latif; Sher Ali; Carlos Augusto Fernandes de Oliveira (Toxicon, 2025)

From 2-D seismic refraction to 3-D subsurface characterization: Unpacking the role of univariate spatial interpolation techniques with borehole validation - Nirandoal Cheng; Mohd Ashraf Mohamad Ismail; Nordiana Mohd Muztaza; Fatin Nadhirah Ahmad Pauzi; Muhammad Taqiuddin Zakaria; Yasuhiro Yokota (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Recent advancements in UiO-66(Zr) MOFs and their derivatives: Designing water-stable membranes for water applications - Yahaya A. Muhammad; Muhammad Sajid; Abubakar Umar; Niaz Ali Khan; Ismail Abdulazeez; Billel Salhi; Nadeem Baig; Wail Falath (Desalination, 2025)

Nonstationarity impacts on the assessment of drought conditions across diverse climate zones of Pakistan - Maryam; Rizwan Aziz; Ismail Yucel; Mahnoosh Moghaddasi; Muhammad Awais (Theoretical and Applied Climatology, 2025)

Projecting future climate extremes in the glacier-fed upper indus basin using machine learning based downscaling of CMIP6 GCMs - Muhammad Amjad Saleem; Muhammad Shoaib; Sarfraz Hashim; Muhammad Shoaib; Hafiz Umar Farid; Muhammad Ismail; Mubashir Ali Ghaffar; Ahmad Mujtaba; Jinwook Lee; Muhammad Azhar Inam; Arshad Ameen (Theoretical and Applied Climatology, 2025)

In silico identification of GTPase inhibitors from selected anti-gonorrheal plants against Neisseria gonorrhoeae - Blessing O. Awoyemi; Badmus Jamiu Damilare; Abdullahi Tunde Aborode; Che Muhammad Khairul Hisyam Ismail; Abdulqohar Adebayo; Haruna Isiyaku Umar; Ibrahim Akindeji Makinde; Ridwan Opeyemi Bello; Sodiq Fakorede; Mohammed M. Alshehri; Ahmed F. Alanazi (The Nucleus, 2025)

Comprehensive investigation of the smouldering characteristics of hemic peat under varying moisture conditions and the combined influence of wind velocity and direction - Nor Azizah Che Azmi; Ahmad Safuan A Rashid; Nazirah Mohd Apandi; Abd Wahid Rasib; Mohd Nazri Mohd Nasir; Adnan Zainorabidin; Mohamad Sofi Mohamed; Muhammad Amir Mat Shah; Diana Che Lat; Afiqah Ismail (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Machine learning-based streamflow projections in the upper indus basin under CMIP6 climate scenarios - Muhammad Amjad Saleem; Muhammad Shoaib; Sarfraz Hashim; Muhammad Shoaib; Hafiz Umar Farid; Mubashir Ali Ghaffar; Muhammad Ismail; Arshad Ameen; Jinwook Lee; Muhammad Azhar Inam; Changhyun Jun (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Mechanistic insights of facile synthesized-solar driven TiO2 intercalated 2D molybdenum disulfide evaporator for one-pot clean water production - Nurul Syazana Fuzil; Nur Hashimah Alias; Nur Hidayati Othman; Muhammad Shafiq Mat Shayuti; Norazah Abd Rahman; Zulkifli Abdul Rashid; Ahmad Fauzi Ismail; Anwar Ul-Hamid; Izumi Ichinose (Desalination, 2025)

The generative adversarial neural network with multi-layers stack ensemble hybrid model for landslide prediction in case of training sample imbalance - Wajid Hussain; Hong Shu; Hasnain Abbas; Sajid Hussain; Isma Kulsoom; Saqib Hussain; Hajra Mustafa; Aftab Ahmed Khan; Muhammad Ismail; Javed Iqbal (Stochastic Environmental Research and Risk Assessment, 2025)

Evaluation of Neuroprotective and Neuroregenerative Potential of NeuroAiD™ II(MLC901) in a Rat Model of Kainic Acid-Induced Spinal Cord Injury - Anam Anjum; Muhammad Dain Yazid; Muhammad Fauzi Daud; Jalilah Idris; Angela Min Hwei Ng; Amaramalar Selvi Naicker; Ohnmar Htwe Rashidah Ismail; Ramesh Kumar Athi Kumar; Yogeswaran Lokanathan (Molecular Neurobiology, 2025)
Excitotoxic damage caused by high extracellular levels of glutamate in the spinal cord results in neuronal loss and severe locomotor impairment. This study investigates the efficacy of NeuroAiD II (MLC901), an herbal formulation, in promoting nerve regeneration following spinal cord injury (SCI) induced by kainic acid (KA). KA, a potent glutamate receptor agonist, causes excitotoxic damage in the spinal cord, leading to neuronal loss and locomotor impairment. To explore the potential of MLC901, KA-injured rats were treated with MLC901, and nerve regeneration was evaluated using various techniques. In this study, KA was administered intrathecally between the T12 and T13 vertebrae in rats, resulting in incomplete paraplegia. MLC901 was then tested for its neuro-regenerative potential. Various assessments were conducted to evaluate the effects of MLC901 treatment, including behavioral, electrophysiological, and histopathological analyses. Behavioral tests, such as the Basso, Beattie, and Bresnahan (BBB) open field test, running wheel, grid walk, inverted grid, and sensory tests, showed significant improvements in locomotor activity in treated rats. Electrophysiological recordings indicated that, while KA injection caused reduced amplitude and delayed latency, MLC901 treatment helped restore lost connections on days 14 and 28. Histopathological and immunohistochemical analyses also revealed improved tissue integrity and neuron survival. The study concludes that MLC901 significantly enhances locomotor recovery, somatosensory evoked potentials, and tissue preservation following SCI. These findings suggest that MLC901 holds promise as a neuro-regenerative therapy for spinal cord injuries.

Heat Tolerance in Omani Lentil Landraces and Their Stress Responses to Elevated Temperatures - Maryam Ismail Al Zeidi; Muhammad Farooq (Journal of Plant Growth Regulation, 2025)

Recent advances in layered double hydroixdes@MXene (LDHs@MXene) composites: Synthesis, properties, and catalytic applications - Sundas Riaz; Sami Ullah; Sanam Bashir; Aziz ur Rehman; Rashid Iqbal; Tayyaba Najam; Mostafa A. Ismail; Md Rezaul Karim; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Applied Clay Science, 2025)

Role of biochar in reducing polyethylene and polylactic acid microplastic co-contamination with antibiotics in soil-vegetable systems - Pengfei Cheng; Junliang Chen; Muhammad Tariq; Lei Tang; Zebin Hong; Babar Iqbal; Ismail Khan; Guanlin Li; Daolin Du; Tongxu Liu (Process Safety and Environmental Protection, 2025)

Persicaria minor F-box protein, PmFBK2 targeted by miR156a in response to MeJA treatment, potentially affects stress-related proteins - Nur-Athirah Abd-Hamid; Muhammad-Izzat Ahmad-Fauzi; Ismanizan Ismail (Journal of Plant Physiology, 2025)

TiN/TiOx/BaTiO3/Pt heterostructure memristors for adaptive neuromorphic systems - Muhammad Ismail; Hyesung Na; Maria Rasheed; Chandreswar Mahata; Hyun-Seok Kim; Heung Soo Kim; Janghyuk Moon; Sungjun Kim (Chemical Engineering Journal, 2025)

Geostatistical and multivariate analysis of phosphate evolution and its relationship with heavy metals in shallow groundwater in a Semi-Arid Basin - Saadu Umar Wali; Noraliani Binti Alias; Abdulqadir Abubakar Usman; Abdullahi Umar; Nasiru Muhammad; Ismail Usman Kaoje; Buhari Samaila; Basiru Aliyu; Habiba Muhammad Ladan; Mudassiru Atiku; Sa’ad Ibrahim (Earth Science Informatics, 2025)

Formation of soluble organics and sugar degradation byproduct during hot compressed water pre-treatment of empty fruit bunch for biogas production - Adila Fazliyana Aili Hamzah; Muhammad Hazwan Hamzah; Khairudin Nurulhuda; Hasfalina Che Man; Muhammad Heikal Ismail; Pau Loke Show (Biomass and Bioenergy, 2025)

Rapid synthesis of charged covalent organic framework for sustainable reverse osmosis membranes - Umar H. Nuhu; Niaz Ali Khan; Ijaz Hussain; Mengying Long; Billel Salhi; Nadeem Baig; Ismail Abdulazeez; Khan Alam; Sikandar Khan; Muhammad Usman; Umer Zahid; Isam H. Aljundi (Desalination, 2025)

Rosmarinic acid attenuates photophobia, hyperalgesia and neuroinflammation during nitroglycerine induced migraine like headache in mice - Maira Anwar; Ismail Badshah; Babar Murtaza; Syed Muzzammil Masaud; Umair Ilyas; Amber Kiyani; Danish Patoli; Muhammad Tariq Khan (Natural Product Research, 2025)

Effect of Gracilaria changii extract and its fraction in reverse cholesterol transport by targeting SR-BI gene - Mohd Rahaizuddin Rani; Ahmad Khusairi Azemi; Kamariah Bakar; Luqman Abu-Bakar; Tengku Sifzizul Tengku Muhammad; Noraznawati Ismail (Natural Product Research, 2025)

A novel three-dimensional graphitic carbon nitride/palladium phosphide heterojunction photocatalyst for enhanced hydrogen production and treatment of industrial dye-polluted water under visible light irradiation - Muhammad Ismail; Youqi Zhu; Hajra; Changliang Du; Lifen Yang; Mingwei Jin; Xilan Ma; Chuanbao Cao; Meishuai Zou (Journal of Environmental Chemical Engineering, 2025)

Tailoring g-C3N4 properties through P and K co-doping: advancing photocatalytic CO2 reduction to CH4 - Ahmed Ismail; Muhammad Zahid; Bilal Ahmad; Salman Hayat; Sher Ali; Syed ul Hasnain Bakhtiar; Abdullah N. Alodhayb; Xiaoqiang Wu; Qaisar Alam; Sharafat Ali; Liang Qiao (Chemical Engineering Journal, 2025)

Pharmacological Potential of Holothuria (Mertensiothuria) leucospilota (Brandt, 1835): Antibacterial Activity Against Methicillin-Resistant Staphylococcus aureus and Metabolite Profile - Abdoulie Ceesay; Muhammad Farhan Nazarudin; Norfarrah Mohamed Alipiah; Ina Salwany Md Yasin; Mohammad Noor Azmai Amal; Mohamad Azzam Mohd Sayuti; Intan Safinar Ismail; Mohammed Aliyu-Paiko (Thalassas: An International Journal of Marine Sciences, 2025)

Assessing the Role of Biostimulants in Affecting the Production of Radish and Eggplant - Muhammad Amjad Bashir; Qurat-Ul-Ain Raza; Abdur Rehim; Hafiz Muhammad Ali Raza; Asad Ismail Noor; Mir Sujaul Islam; Faiz-Ul-Hassan; Muhammad Zafar-Ul-Hye; Yucong Geng (Journal of Soil Science and Plant Nutrition, 2025)

Physiological responses of hybrid grouper (Epinephelus fuscoguttatus X Epinephelus lanceolatus) to temperature fluctuation stress revealed by LCMS/MS-based mucus and sera metabolomics - Ellia Kartini Mujar; Saleema Matusin; Nur Syahirah Yahya; Muhammad Safwan Ahamad Bustamam; Annie Christianus; Khozirah Shaari; Nur Kartinee Kassim; Faridah Abas; Jen Kit Tan; Intan Safinar Ismail (Fish Physiology and Biochemistry, 2025)

Marine landscape mapping for ecologically relevant habitat suitability modelling - Bryan Yong; Khaira Ismail; Azizi Ali; Rozaimi Che Hasan; Muhammad Abdul Hakim Muhamad (Earth Science Informatics, 2025)

Occurrence of aflatoxins and effect of preventive practices to inhibit fungal growth and aflatoxin production in leftover flat bread/chapati used as animal feed and stored in Pakistani dairy farms - Mavra Amin; Amir Ismail; Iqra Naeem; Usama Nasir; Muhammad Riaz; Yun Yun Gong; Sher Ali; Michael N. Routledge; Amna Iqbal; Asifa Saif; Carlos Augusto Fernandes Oliveira (Journal of Stored Products Research, 2025)

Development and performance of sugar palm nano-fibrillated cellulose reinforced rubber membranes for efficient palm oil mill effluent treatment - A.S. Norfarhana; R.A. Ilyas; Abu Hassan Nordin; Ya Muhammad Nazir Syah Ismail; Norzita Ngadi; Mohd Hafiz Dzarfan Othman (Journal of Water Process Engineering, 2025)

Recent advances in recycling and upcycling of hazardous plastic waste: A review - Siti Zulaika Khairul Anuar; Abu Hassan Nordin; Siti Muhamad Nur Husna; Abdul Hafidz Yusoff; Syafikah Huda Paiman; Siti Fadilla Md Noor; Muhammad Luqman Nordin; Siti Nurlia Ali; Ya Mohammad Nazir Syah Ismail (Journal of Environmental Management, 2025)

Hexagonal boron nitride: From fundamentals to applications - Sajjad Ali; Pir Muhammad Ismail; Muhammad Humayun; Mohamed Bououdina (Desalination, 2025)

ENSO teleconnections and predictability of the boreal summer temperature over the Arabian Peninsula in C3S and Saudi-KAU seasonal forecast systems - Mansour Almazroui; M. Salman Khalid; Muhammad Adnan Abid; Irfan Ur Rashid; Shahzad Kamil; Haroon Siddiqui; M. Nazrul Islam; Muhammad Ismail; Muhammad Azhar Ehsan; Enda O'Brien; Mazen Asiri; Rayees Ahmed; et al. (Atmospheric Research, 2025)

A novel CLRN2 variant: expanding the mutation spectrum and its critical role in isolated hearing impairment - Farooq Ahmad; Arif Mahmood; Ibrahim Abdullah Almazni; Afnan Mohammed Shakoori; Fatemah Alhakami; Qamre Alam; Muhammad Ismail; Muhammad Umair (Genes & Genomics, 2025)

Supplementing high-fiber olive pomace and multi-enzymes to broiler chicken’s diet can improve health and performance - Osama Rahman Ghaffar; Dastan Mohammed Khoshnaw; Omer Rasool Ahmed; Sarwar Omer Aziz; Asrin Abdollahi; Nihayat Ibrahim Mohammed; Karzan Kareem Saleh; Niga Rzgar Ahmad; Mzhda Mohammed Majeed; Shiraz Ismail Muhammad; Srwsht Farhad Osman; Hawkar Azad Khdir (Tropical Animal Health and Production, 2025)

Exploring the diversity of scorpions in Lahore Division, Punjab: an ecological approach - Muhammad Mohsin Ahsan; Abdul Khalaq; Hafiz Muhammad Tahir; Muhammad Ismail; Muhammad Samiullah; Maira Noor; Safia Bibi (International Journal of Tropical Insect Science, 2025)

A comprehensive review on guava: Nutritional profile, bioactive potential, and health-promoting properties of its pulp, peel, seeds, pomace and leaves - Farwa Iqbal Khan; Saeed Akhtar; Muhammad Qamar; Tariq Ismail; Wisha Saeed; Tuba Esatbeyoglu; Seid Mahdi Jafari (Trends in Food Science & Technology, 2025)

A review of recent advances in green and sustainable technologies for removing 4-nitrophenol from the water and wastewater - Hamza Badamasi; Zain Naeem; Giorgio Antoniolli; Avvaru Praveen Kumar; Abdul Ademola Olaleye; Ismail Shina Sadiq; Naseer Inuwa Durimin-iya; Muhammad Salman Khan (Sustainable Chemistry and Pharmacy, 2025)

Comet Assay and Micronucleus Test in Circulating Erythrocytes of Ctenopharyngodon idella Exposed to Nickel Oxide Nanoparticles - Jamshid Khan; Nazish Shah; Farmanullah Dawar; Iqra Irfan; Adil Jan; Muhammad Ismail Khan; Muhammad Khisroon (Biological Trace Element Research, 2025)

Dust over Saudi Arabia from multisource data: case studies in winter and spring - Mazen E. Assiri; M. Nazrul Islam; Md Arfan Ali; Arjan O. Zamreeq; Ayman S. Ghulam; Muhammad Ismail (Air Quality, Atmosphere & Health, 2025)

Phytotreatment of tofu effluent using water lettuce (Pistia stratiotes) and potential of biogas production from resultant biomass - Setyo Budi Kurniawan; Muhammad Fauzul Imron; Rikky Ramadhan Mustofa; Dhuroton Najiya; Nor Sakinah Mohd Said; Junaidah Buhari; Hajjar Hartini Wan Jusoh; Azimah Ismail (Journal of Water Process Engineering, 2025)

Nonstationarity assessment in extreme temperatures and its association with antecedent soil moisture levels across diverse climate zones in Pakistan - Darakshan Naeem; Rizwan Aziz; Mahnoosh Moghaddasi; Ismail Yucel; Muhammad Awais (Theoretical and Applied Climatology, 2025)

H2S and SO2 toxic gases removal using date palm-tree branches based activated carbon: experimental findings and machine learning (ML) modeling - Usman M. Ismail; Minaam Hussaini; Muhammad S. Vohra (Environment, Development and Sustainability, 2024)

Retraction Note: Protective effect of myricetin on nonylphenol-induced testicular toxicity: biochemical, steroidogenic, hormonal, spermatogenic, and histological-based evidences - Muhammad Umar Ijaz; Haseeb Anwar; Shabnoor Iqbal; Hammad Ismail; Asma Ashraf; Shama Mustafa; Abdul Samad (Environmental Science and Pollution Research, 2024)

Advancing photocatalytic membrane for efficient endocrine disrupting compounds removal: Progresses and challenges - Muhammad Hafizuddin Hazaraimi; Pei Sean Goh; Woei Jye Lau; Ahmad Fauzi Ismail; Norbaya Hashim; Nirmala Devi Kerisnan@Kerishnan; Nasehir Khan E.M. Yahaya; Raja Baharudin Raja Mamat (Journal of Water Process Engineering, 2024)

Fabrication and characterization of bioactive curdlan and sodium alginate films for enhancing the shelf life of Volvariella volvacea - Asif Ali Khan; Feng-Jie Cui; Muhammad Wajid Ullah; Abdul Qayum; Ibrahim Khalifa; Syed Asim Shah Bacha; Zheng-Zi Ying; Ismail Khan; Umar Zeb; Abdullah A. Alarfaj; Mohammad Javed Ansari; Yan Yang; et al. (Food Bioscience, 2024)

Adenosine A2AR in viral immune evasion and therapy: unveiling new avenues for treating COVID-19 and AIDS - Muhammad Atif; Abdullah Alsrhani; Farrah Naz; Sajjad Ullah; Abualgasim Elgaili Abdalla; Muhammad Ikram Ullah; Bi Bi Zainab Mazhari; Lienda Bashier Eltayeb; Ismail Hamad; Hasan Ejaz (Molecular Biology Reports, 2024)

Deciphering the differential expression patterns of yield-related negative regulators in hexaploid wheat cultivars and hybrids at different growth stages - Muhammad Jawad Akbar Awan; Muhammad Awais Farooq; Rubab Zahra Naqvi; Umer Karamat; Sayyad Ali Raza Bukhari; Muhammad Abu Bakar Waqas; Muhammad Arslan Mahmood; Muhammad Ismail Buzdar; Awais Rasheed; Imran Amin; Nasir A. Saeed; Shahid Mansoor (Molecular Biology Reports, 2024)

Bacillus spore germination: mechanisms, identification, and antibacterial strategies - Lihua Fan; Yanru Zhang; Balarabe Bilyaminu Ismail; Aliyu Idris Muhammad; Guoliang Li; Donghong Liu (Critical Reviews in Food Science and Nutrition, 2024)

Enhancing Surface Properties of Circular Carbon Biochar Derived from Spent Coffee Beans Through ZnCl2/KOH Activation - Gowthami D.; R. K. Sharma; M. Khalid; Muhammad Yusri Ismail (BioEnergy Research, 2024)

Efficacy of Melia azedarach leaf extract in different solvents against Heterotermes indicola Wasmann (Blattodea: Rhinotermitidae) using non-durable wooden blocks under laboratory and field conditions - Muhammad Afzal; Hamid-ur Rehman; Ismail Zeb; Naveeda Akhtar Qureshi (South African Journal of Botany, 2024)

Exploring fruit ripening methods: Conventional, artificial, and novel approaches for quality and health - Usama Nasir; Amir Ismail; Muhammad Riaz; Kashif Razzaq; Sajid Ali; Ajaz Hussain; Mavra Ameen; Asifa Saif; Farwa Aslam; Carlos Augusto Fernandes de Oliveira (Food Control, 2024)

Impacts of installation methods on the thermal performance of lightweight exterior cladding panels incorporating PCM: An experimental evaluation - Zeyad Amin Al-Absi; Mohd Isa Mohd Hafizal; Muhammad Asif; Aasem Alabdullatief; Mazran Ismail (Building and Environment, 2024)

A multi-sensor drought index for improved agricultural drought monitoring and risk assessment in the heterogeneous landscapes of the China–Pakistan Economic Corridor (CPEC) - Muhammad Ismail; Yi Li; Ben Niu; Mubashir Ali Ghaffar; Muhammad Amjad Saleem; Kadambot H.M. Siddique (Atmospheric Research, 2024)

Evaluating the biological activity of rolB-transgenic Nicotiana tabacum plants using phytochemical and pharmacological approaches - Afshan Anwar; Shabana Haneef; Hammad Ismail; Muhammad Zeeshan Bhatti; Nazif Ullah; Iram Murtaza; Bushra Mirza (Plant Biosystems, 2024)

Electrosorption-driven selective thorium removal from radioactive wastewater with phosphate – Incorporated g-C3N4 electrode - Nabiha Mohd Yussuf; Aznan Fazli Ismail; Muhammad Abdullah Rahmat; Nurul Aida Mohamed (Journal of Environmental Chemical Engineering, 2024)

Machine learning modeling and statistical optimization of dye removal from contaminated water using CTAB-functionalized graphene oxide - Sally AlNaimat; Usman M. Ismail; Ahmed I. Ibrahim; Abdimalik Muse; Kashif Faheem; Mohamed Mustafa; Muhammad S. Vohra; Sagheer A. Onaizi (Water, Air, & Soil Pollution, 2024)

Fine-tuning plant valuable secondary metabolite biosynthesis via small RNA manipulation: strategies and potential - Nur Irdina Izzatie Mohd Zahid; Syed Muhammad Iqbal Syed Othman; Arif Faisal Mustaffa; Ismanizan Ismail; Muhamad Hafiz Che-Othman (Planta, 2024)

Recent advances of MXene@MOF composites for catalytic water splitting and wastewater treatment approaches - Samreen Afzal; Aziz ur Rehman; Tayyaba Najam; Ismail Hossain; Mostafa A.I. Abdelmotaleb; Sundas Riaz; Md Rezaul Karim; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Chemosphere, 2024)

Microplastic and cadmium contamination: Impact on the soil by inhibiting the growth of pak choi (Brassica rapa subsp. chinensis) - Guanlin Li; Xinran Cui; Muhammad Tariq; Ismail Khan; Ali Raza Khan; Sami Al Obaid; Mohammad Javed Ansari; Huan Zhou; Babar Iqbal; Xin Zhao (Process Safety and Environmental Protection, 2024)

Strengthening education and training programmes for medical physics in Asia and the Pacific: the IAEA non-agreement technical cooperation (TC) regional RAS6088 project - Noriah Jamal; Anchali Krisanachinda; Virginia Tsapaki; Md Rafiqul Islam; Supriyanto Pawiro; Muhammad Al Omari; Chai Hong Yeong; Thinn Thinn Myint; Muhammad Basim Kakakhel; Mohammad Hassan Kharita; Cheow Lei James Lee; Anas Ismail; et al. (Physical and Engineering Sciences in Medicine, 2024)

Secondary Metabolites Mediated Reproductive Tolerance Under Heat Stress in Plants - Abdul Rehman; Ismail Khan; Muhammad Farooq (Journal of Plant Growth Regulation, 2024)

A potential toxicological risk assessment of heavy metals and pesticides in irrigated rice cultivars near industrial areas of Dhaka, Bangladesh - Muhammad Nurul Huda; Mohammad Harun-Ur-Rashid; Anowar Hosen; Mahafuga Akter; Md. Mominul Islam; Sharmin Zaman Emon; Asma Rahman; Zuairia Binte Jashim; Saif Shahrukh; Mohammad Ismail (Environmental Monitoring and Assessment, 2024)

Comparative analysis of physicochemical properties and biological activities of crude polysaccharides isolated from selected Auricularia cornea strains - Asif Ali Khan; Fang-Jie Yao; Feng-Jie Cui; Yu Li; Lixin Lu; Ismail Khan; Abdul Jalal; Ming Fang; Khulood Fahad Alabbosh; Mohamed F. Awad; Noureddine Elboughdiri; Muhammad Wajid Ullah (Food Bioscience, 2024)

Eco-friendly approaches for mitigating plastic pollution: advancements and implications for a greener future - Ayesha Safdar; Fatima Ismail; Maryem Safdar; Muhammad Imran (Biodegradation, 2024)

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Aflatoxins in the rice production chain: A review on prevalence, detection, and decontamination strategies - Iqra Naeem; Amir Ismail; Muhammad Riaz; Mubashir Aziz; Kashif Akram; Muhammad A. Shahzad; Mavra Ameen; Sher Ali; Carlos A.F. Oliveira (Food Research International, 2024)

Advancement in modern breeding and genomic approaches to accelerate rice improvement: speed breeding focus - Fatin’Alyaa Zainuddin; Mohd Razi Ismail; Muhammad Asyraf Md Hatta; Shairul Izan Ramlee (Euphytica, 2024)

Maximizing energy via solar‐powered smart irrigation: An approach utilizing a single‐axis solar tracking mechanism - Firas Basim Ismail; Muhammad Aqil Afham Rahmat; Hussein A. Kazem; Abdulkareem Sh. Mahdi Al‐Obaidi; Muhammad Syauqi Ridwan (Irrigation and Drainage, 2024)
This study presents and assesses the novelty of a cutting‐edge solar‐powered automated irrigation system that incorporates a single‐axis solar tracker. The research entails the meticulous development of a prototype, followed by comprehensive experimental scrutiny spanning 3 days, from 8:00 AM to 6:00 PM. In a unique approach, we benchmark the findings against previous research endeavours, highlighting the transformative potential of our innovative design. Our innovative system harnesses a singular‐axis solar tracking mechanism alongside moisture sensors and a water pump relay module, resulting in the creation of an autonomous irrigation system perpetually powered by solar energy. The results are noteworthy, showcasing the capability of a solar panel equipped with single‐axis tracking to significantly boost photovoltaic output power. This configuration attains a remarkable 65% increase in total output power and a substantial improvement over the modest 52%–53% performance of fixed solar panels. This substantial divergence translates to a noteworthy 12%–13% difference in efficacy, underscoring the pioneering nature of our research. The zenith of power output, ranging between 3.16 and 3.68 W, transpires from noon to 2:00 PM, further illustrating the system's viability. The integrated water pump exhibits commendable efficiency, attaining levels as high as 75%. This revelation underscores the transformative potential of automated irrigation systems endowed with single‐axis solar tracking technology, auguring amplified system performance and heralding a new era of sustainable agricultural practices.

Investigating the comparative utility of ECMWF precipitation forecasts as an alternative to reanalysis data - Muhammad Amjad; M. Tugrul Yilmaz; Ismail Yucel; Koray K. Yilmaz; Kurtuluş Öztürk (Hydrological Sciences Journal, 2024)

Emerging interest of gold-carbon nanocomposites in water remediation: A new way forward - Santheraleka Ramanathan; Woei Jye Lau; Pei Sean Goh; Muhammad Firdaus Omar; Michael C. Breadmore; Ahmad Fauzi Ismail; Hong Heng See (Journal of Environmental Chemical Engineering, 2024)

Forward osmosis as a contemporary treatment solution for mitigating radionuclide pollution in water bodies - Muhammad ‘Adli Nor Azman; Pei Sean Goh; Ahmad Fauzi Ismail; Khairulnadzmi Jamaluddin; Keng Yinn Wong; Ahmad Syazwan Sahril (Journal of Environmental Chemical Engineering, 2024)

Adsorptive removal of heavy metals from aqueous solutions: Progress of adsorbents development and their effectiveness - Usman M. Ismail; Muhammad S. Vohra; Sagheer A. Onaizi (Environmental Research, 2024)

Molecular mechanisms of morphine tolerance and dependence; novel insights and future perspectives - Ismail Badshah; Maira Anwar; Babar Murtaza; Muhammad Imran Khan (Molecular and Cellular Biochemistry, 2024)

Genetic variation of nutritional quality traits in grains of Lablab (Lablab purpureus L. Sweet) accessions: implications for forage improvement program - Swidiq Mugerwa; Julius Pyton Sserumaga; Siraj Ismail Kayondo; Muhammad Kiggundu; Abasi Kigozi; Clementine Namazzi; Herbert Galinya; James Bugeza; Hussein Kato Walusimbi; Allen Molly; Geofrey Nviiri; Matovu Moses (Journal of Crop Science and Biotechnology, 2024)

Soil microplastics: Impacts on greenhouse gasses emissions, carbon cycling, microbial diversity, and soil characteristics - Ismail Khan; Muhammad Tariq; Khulood Fahad Alabbosh; Abdul Rehman; Abdul Jalal; Asif Ali Khan; Muhammad Farooq; Guanlin Li; Babar Iqbal; Naveed Ahmad; Khalid Ali Khan; Daolin Du (Applied Soil Ecology, 2024)

Mechanical scratch injury on differentiated motor neuron of NSC-34 cells as an in vitro model for evaluation of neuroregeneration potential of NeuroAiD II (MLC901) - Anam Anjum; Muhammad Dain Yazid; Muhammad Fauzi Daud; Jalilah Idris; Angela Min Hwei Ng; Amaramalar Selvi Naicker; Ohnmar Htwe Ismail; Ramesh Kumar Athi Kumar; Yogeswaran Lokanathan (In vitro models, 2024)

Fostering sustainability and green innovation reporting in manufacturing firms: an investigation of barriers through ISM-MICMAC approach - Rehana Naheed; Muhammad Waqas; Naveed Ahmad; Muzaffar Iqbal; Muhammad Ismail (Environment, Development and Sustainability, 2024)

Microplastic contamination in the agricultural soil—mitigation strategies, heavy metals contamination, and impact on human health: a review - Muhammad Tariq; Babar Iqbal; Ismail Khan; Ali Raza Khan; Eun Hea Jho; Abdul Salam; Huan Zhou; Xin Zhao; Guanlin Li; Daolin Du (Plant Cell Reports, 2024)

Medicinal Polypharmacology in the Clinic – Translating the Polypharmacolome into Therapeutic Benefit - Muhammad Rafehi; Marius Möller; Wouroud Ismail Al-Khalil; Sven Marcel Stefan (Pharmaceutical Research, 2024)
Drugs with multiple targets, often annotated as ‘unselective’, ‘promiscuous’, ‘multitarget’, or ‘polypharmacological’, are widely considered in both academic and industrial research as a high risk due to the likelihood of adverse effects. However, retrospective analyses have shown that particularly approved drugs bear rich polypharmacological profiles. This raises the question whether our perception of the specificity paradigm (‘one drug-one target concept’) is correct – and if specifically multitarget drugs should be developed instead of being rejected. These questions provoke a paradigm shift – regarding the development of polypharmacological drugs not as a ‘waste of investment’, but acknowledging the existence of a ‘lack of investment’. This perspective provides an insight into modern drug development highlighting latest drug candidates that have not been assessed in a broader polypharmacology-based context elsewhere embedded in a historic framework of classical and modern approved multitarget drugs. The article shall be an inspiration to the scientific community to re-consider current standards, and more, to evolve to a better understanding of polypharmacology from a challenge to an opportunity.

Effects of acclimation temperature on growth, physiology and thermal tolerance of the juvenile grass carp Ctenopharyngodon idella - Fahim Ullah Khan; Waqar Younas; Yueyong Shang; Zhihan Tu; Muhammad Ismail Khan; Amina Zuberi; Youji Wang (Aquaculture, 2024)

Scorpion sting in Hafizabad, Pakistan: Facility based epidemiological study - Muhammad Mohsin Ahsan; Zoya Gulzar; Hafiz Muhammad Tahir; Aamir Ali; Muhammad Ismail; Muhammad Khalid Mukhtar; Zain Ul Abdin (Toxicon, 2024)

Spatially explicit estimation of freshwater fish stock biomass with limited data: A case study of an endangered endemic fish on the Tibetan Plateau, China - Kunyuan Wanghe; Shahid Ahmad; Xin Zhou; Fei Tian; Sijia Liu; Bingzheng Zhou; Ghulam Nabi; Guojie Wang; Kemao Li; Shenglong Jian; Huamin Jiang; Shengxue Chen; et al. (Science of The Total Environment, 2024)

An explainable two-stage machine learning approach for precipitation forecast - Ali Ulvi Galip Senocak; M. Tugrul Yilmaz; Sinan Kalkan; Ismail Yucel; Muhammad Amjad (Journal of Hydrology, 2023)

Rainwater harvesting for agriculture development using multi-influence factor and fuzzy overlay techniques - Xiangtian Zheng; Abid Sarwar; Fakhrul Islam; Abdul Majid; Aqil Tariq; Muhammad Ali; Shazia Gulzar; Muhammad Ismail Khan; Muhammad Akmal Sardar Ali; Muhammad Israr; Ahsan Jamil; Muhammad Aslam; et al. (Environmental Research, 2023)

Elettaria cardamomum seed extract synthesized silver nanoparticles for efficient catalytic reduction of toxic dyes - Muhammad Zahid; Abdul Sattar M. Segar; Shaymaa Al-Majmaie; A.H. Shather; Muhammad Farooq Khan; Arnold C. Alguno; Rey Y. Capangpangan; Ahmed Ismail (Environmental Nanotechnology, Monitoring & Management, 2023)

Extraction of lignin from sugarcane trash and its potency as biosurfactant - Azizatul Karimah; Izdihar Khosani Hani; Raden Permana Budi Laksana; Maya Ismayati; Nissa Nurfajrin Solihat; Fahriya Puspita Sari; Ismail Budiman; Muhammad Ghozali; Obie Farobie; Deded Sarip Nawawi; Muhammad Adly R. Lubis; M. Hazwan Hussin; et al. (Bioresource Technology Reports, 2023)

Selective formation of fuel BXT compounds from catalytic hydrodeoxygenation of waste biomass over Ni-decorated beta-zeolite - Ola Ismail; Ala Hamid; Labeeb Ali; Toyin Shittu; Mohamed S. Kuttiyathil; Muhammad Z. Iqbal; Abbas Khaleel; Mohammednoor Altarawneh (Bioresource Technology Reports, 2023)

A Comprehensive Review on Handling of Plastic Waste For Energy Generation—Current Status and Future Challenges - Abdul Sattar Jatoi; Jawad Ahmed; Nabisab Mujawar Mubarak; Muhammad Shuaib Shaikh; Sandeep Kumar; Muhammad Ismail Ahmed; Rama Rao Karri (Water, Air, & Soil Pollution, 2023)

Assessment of rainwater harvesting potential for urban area under climate and land use changes using geo-informatics technology - Saif Haider; Muhammad Umer Masood; Muhammad Rashid; Tauqeer Ali; Chaitanya B. Pande; Fahad Alshehri; Ismail Elkhrachy (Urban Climate, 2023)

Synergistic effect of Bacillus subtilis and benzothiadiazole (Bion®) on the suppression of Fusarium oxysporum and the enhancement of disease resistance in Capsicum annuum - Kamal A. M. Abo-Elyousr; Nashwa M.A Sallam; Magdy A. A Mousa; Muhammad Imran; Ismail R. Abdel-Rahim (Journal of Plant Pathology, 2023)

Occurrence and characterization of Alternaria alternata causing leaf spot of soybean (Glycine max) in Pakistan - Muhammad Ismail Buzdar; Nasim Ahmed; Muhammad Jawad Akbar Awan; Saleem. Ur-Rahman; Muhammad Abu Bakar Waqas; Ghulam Raza; Fathia Mubeen; Shahid Mansoor; Imran Amin (Journal of Plant Pathology, 2023)

Administration of α-lipoic acid and silymarin attenuates aggression by modulating endocrine, oxidative stress and inflammatory pathways in mice - Adnan Karim; Fareeha Anwar; Uzma Saleem; Saniya Fatima; Tariq Ismail; Ahmad J. Obaidullah; Rana O. Khayat; Moneerah J. Alqahtani; Ifat Alsharif; Haroon Khan; Celia Vargas-De-La-Cruz; Muhammad Ajmal Shah (Metabolic Brain Disease, 2023)

Enhancing the stability of shale in water-based fluid with polyethylene glycol/nanosilica composite grafted with sodium dodecyl sulfate - Shafeeg Omer Blkoor; Muhammad Noorul Anam Bin Mohd Norddin; Issham Ismail; Jeffrey Onuoma Oseh; Saeed S. Basaleh; Abdul Rahim Bin Risal; Mohd Firdaus Bin Sariman; Eugene N. Ngouangna (Arabian Journal of Geosciences, 2023)

Prophylactic effects of dietary Isochrysis galbana on immersion-challenged red hybrid tilapia (Oreochromis spp.) with Streptococcus agalactiae by spleen-NMR-metabolomics - Muhammad Safwan Ahamad Bustamam; Khozirah Shaari; Chong Chou Min; Md Shirajum Monir; Hamza Ahmed Pantami; Intan Safinar Ismail (Aquaculture International, 2023)

Influence of soil microplastic contamination and cadmium toxicity on the growth, physiology, and root growth traits of Triticum aestivum L. - Babar Iqbal; Qaiser Javed; Ismail Khan; Muhammad Tariq; Naveed Ahmad; Hosam O. Elansary; Arshad Jalal; Guanlin Li; Daolin Du (South African Journal of Botany, 2023)

Linking diagenesis and reservoir quality to depositional facies in marginal to shallow marine sequence: An example from the Campano-Maastrichtian Gombe Sandstone, Northern Benue Trough, NE Nigeria - Abdulwahab M. Bello; Musa B. Usman; Muhammad A. Ismail; Shehu Mukkafa; Usman Abubakar; Ibrahim A. Kwami; Khalid Al-Ramadan; Abduljamiu O. Amao; Murtada Al-Hashem; Anas M. Salisu; Aliyuda Kachalla; Muhammad B. Abubakar; et al. (Marine and Petroleum Geology, 2023)

Biostratigraphy, organic petrography and carbon isotope chemostratigraphy of the Ordovician-Silurian black shales from the Northwestern Domain of Peninsular Malaysia - Muhammad Aqqid Saparin; Khairul Azlan Mustapha; Mohd Suhaili Ismail (International Journal of Coal Geology, 2023)

Deciphering genetic-by-environment interaction, pests and disease's reaction, grain quality, and response to fertilizer for targeting high-yielding rice varieties - Trias Sitaresmi; Nafisah Nafisah; Untung Susanto; Rahmini Rahmini; Yuni Widyastuti; Bram Kusbiantoro; Muhammad Ismail Wahab; Aris Hairmansis; Yudhistira Nugraha (Ecological Genetics and Genomics, 2023)

Transport and depositional processes of organic matter evaluated by biomarker profiles in Miocene turbiditic sequences from Hokkaido, Japan - Muhammad Adam Ismail; Hiroyasu Asahi; Ken Sawada (Sedimentary Geology, 2023)

Estimation of component-wise runoff contribution using temperature index approach, in a snow- and glacier-fed transboundary Shyok River catchment of the Upper Indus Basin - Muhammad Umar Farooq; Muhammad Ashiq Kharal; Wolfgang Bogacki; Muhammad Fraz Ismail; Asif Mehmood (Arabian Journal of Geosciences, 2023)

Morphological and molecular observations of nematodes belonging to the family Hoplolaimidae from the Thar Desert, Pakistan - Ramzan Ali; Ebrahim Shokoohi; Erum Iqbal; Muhammad Ismail Bhatti; Saboohi Raza (Biologia, 2023)

Formation of value-added products from the pyrolysis of date pits: A combined experimental–DFT approach - Ola Ismail; Labeeb Ali; Mohamed Shafi Kuttiyathil; Muhammad Z. Iqbal; Abbas Khaleel; Mohammednoor Altarawneh (Biomass and Bioenergy, 2023)

Assessing the impact of urbanization on groundwater quality of lahore region, Pakistan - Sadia Ismail; Muhammad Farooq Ahmed; Muhammad Zubair Abu Bakar (Environmental Science and Pollution Research, 2023)

Balancing economic growth and environmental protection: A sustainable approach to Malaysia's rare-earth industry - Eli Syafiqah Aziman; Aznan Fazli Ismail; Muhammad Abdullah Rahmat (Resources Policy, 2023)

A crucial review on the challenges and recent gas membrane development for biogas upgrading - Nur Fajrina; Norhaniza Yusof; Ahmad Fauzi Ismail; Farhana Aziz; Muhammad Roil Bilad; Meshel Alkahtani (Journal of Environmental Chemical Engineering, 2023)

MoS2-TiO2 coated PVDF-based hollow fiber membranes for permeate flux enhancement in membrane distillation - Nurul Syazana Fuzil; Nur Hidayati Othman; Nur Hashimah Alias; Fauziah Marpani; Muhammad Shafiq Mat Shayuti; Munawar Zaman Shahruddin; Mohd Rizuan Mohd Razlan; Norazah Abd Rahman; Woei Jye Lau; Mohd Hafiz Dzarfan Othman; Ahmad Fauzi Ismail; Tutuk Djoko Kusworo; et al. (Journal of Environmental Chemical Engineering, 2023)

Bibliometric approach to trehalulose research trends for its potential health benefits - Muhammad Faiz Zulkifli; Mohanasundarapandian Sivakumar; M. Maulidiani; Wan Iryani Wan Ismail (Food Bioscience, 2023)

Engineering of oxygen vacancy defect in CeO2 through Mn doping for toluene catalytic oxidation at low temperature - Ahmed Ismail; Muhammad Zahid; Sharafat Ali; Syed ul Hasnain Bakhtiar; Nauman Ali; Adnan Khan; Yujun Zhu (Environmental Research, 2023)

A window into the future: case study of long-term radiological risk modelling posed by unregulated mining waste repurposing activities - Muhammad Abdullah Rahmat; Aznan Fazli Ismail; Nursyamimi Diyana Rodzi; Eli Syafiqah Aziman; Syazwani Mohd Fadzil; Norsyahidah Mohd Hidzir; Mohd Idzat Idris; Irman Abdul Rahman; Faizal Mohamed (Environmental Monitoring and Assessment, 2023)

Novel evolutionary-optimized neural network for predicting landslide susceptibility - Rana Muhammad Adnan Ikram; Imran Khan; Hossein Moayedi; Atefeh Ahmadi Dehrashid; Ismail Elkhrachy; Binh Nguyen Le (Environment, Development and Sustainability, 2023)

A review on revolutionary technique for phosphate removal in wastewater using green coagulant - Amina A. Owodunni; Suzylawati Ismail; Setyo Budi Kurniawan; Azmi Ahmad; Muhammad Fauzul Imron; Siti Rozaimah Sheikh Abdullah (Journal of Water Process Engineering, 2023)

MOF based composites with engineering aspects and morphological developments for photocatalytic CO2 reduction and hydrogen production: A comprehensive review - Muhammad Tahir; Bilkis Ajiwokewu; Anifat Adenike Bankole; Ola Ismail; Hebah Al-Amodi; Naveen Kumar (Journal of Environmental Chemical Engineering, 2023)

3D porous superoleophilic/hydrophobic grapefruit peel aerogel for efficient removal of emulsified-oil from water - Muhammad Imran; Ashraful Islam; Fatima Ismail; Panyue Zhang; Majid Basharat; Muhammad Ikram; Ahmed Uddin; Shah Zeb; Qadeer-Ul Hassan; Yongxiang Gao (Journal of Environmental Chemical Engineering, 2023)

Amentoflavone derivatives significantly act towards the main protease (3CLPRO/MPRO) of SARS-CoV-2: in silico admet profiling, molecular docking, molecular dynamics simulation, network pharmacology - Dipta Dey; Rajib Hossain; Partha Biswas; Priyanka Paul; Md. Aminul Islam; Tanzila Ismail Ema; Bibhuti Kumar Gain; Mohammad Mehedi Hasan; Shabana Bibi; Muhammad Torequl Islam; Md. Ataur Rahman; Bonglee Kim (Molecular Diversity, 2023)

Seed-borne Curvularia lunata deteriorating seed health and germination of soybean - Muhammad Ismail Buzdar; Muhammad Jawad Akbar Awan; Saleem Ur Rahman; Rubab Zahra Naqvi; Ghulam Raza; Shahid Mansoor; Imran Amin (Biologia, 2023)

Impact of differential occupational LPG exposure on cardiopulmonary indices, liver function, and oxidative stress in Northwestern city of Nigeria - Abubakar Usman Ismail; Salisu Ahmed Ibrahim; Mahdi Dissi Gambo; Ramlah Farouq Muhammad; Murtala Muhammad Badamasi; Ibrahim Sulaiman (Science of The Total Environment, 2023)

Rapeseed increases cadmium concentration of wheat in a rotation system through suppressing root mycorrhizal activity of wheat - Muhammad Asif; Idil Ertem; Huseyin Beyaz; Cynthia A. Grant; Hans Lambers; Ismail Cakmak (Plant and Soil, 2023)

Biochar Amendment in Combination with Endophytic Bacteria Stimulates Photosynthetic Activity and Antioxidant Enzymes to Improve Soybean Yield Under Drought Stress - Fahim Nawaz; Rashid Rafeeq; Sadia Majeed; Muhammad Shoaib Ismail; Muhammad Ahsan; Khawaja Shafique Ahmad; Ahsan Akram; Ghulam Haider (Journal of Soil Science and Plant Nutrition, 2023)
The beneficial effects of biochar (BC) and plant growth-promoting bacteria (PGPR) to increase crop yields under harsh environments have been widely reported. However, the knowledge on the synergistic effects of BC and PGPR to induce drought tolerance in oilseeds is scant. In the present study, the effects of cotton sticks derived BC together with PGPR strains ( Paraburkholderia phytofirmans and Bacillus sp.) were examined in water-stressed soybean plants. Initially, the BC application rates (1% and 2%) for soybean were optimized in a pilot experiment (experiment I), and the most effective level (1%) was selected for further studies together with PGPR in the second experiment. The soybean plants were raised in pots under semi-controlled conditions and were subjected to drought stress (25–30% water holding capacity) at pod formation stage. In comparison with control, the drought-mediated decrease in photosynthetic pigments and gas exchange characteristics was markedly lower in BC and PGPR-treated plants. However, the maximum increase in photosynthetic (12–30%) and the enzymatic antioxidant activities (5–20%) was recorded in plants treated with BC + P. phytofirmans , whereas no further significant increase was observed in plants treated with combined BC and Bacillus sp. under water deficit conditions. Similarly, the combined BC and P. phytofirmans application considerably increased the grain yield (14%) under drought stress conditions. We conclude that the combined application of BC + P. phytofirmans could be utilized as an effective strategy to improve soybean yield in dry arid regions.

Experimental Characterization-Based Machine Learning Modeling for the Estimation of Geotechnical Properties of Clay Liners - Hafiz Muhammad Awais Rashid; Muhammad Sufyan; Atif Ismail; Umer Waqas (Geotechnical and Geological Engineering, 2023)

Numerical investigation of fully confined RC column with carbon fiber reinforced polymer when expose to fire - Nur Aqilah Zakaria; Ruqayyah Ismail; Fariz Aswan Ahmad Zakwan; Hazrina Ahmad; Muhamad Firdaus Rosle; Mohd Hisbany Mohd Hashim; Raizal Saifulnaz Muhammad Rashid (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Centella asiatica (L.) Urb. Extract ameliorates branched-chain amino acid (BCAA) metabolism in acute reserpine-induced stress zebrafish model via 1H Nuclear Magnetic Resonance (NMR)-based metabolomics approach - Fauziahanim Zakaria; Muhammad Tayyab Akhtar; Wan Ibrahim Wan Norhamidah; Abu Bakar Noraini; Azira Muhamad; Shamarina Shohaimi; Maulidiani; Hafandi Ahmad; Intan Safinar Ismail; Nor Hadiani Ismail; Khozirah Shaari (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

The use of magnetic and geoelectrical methods to locate buried ancient artificial canals and wells around the cultural heritage of Indrapatra Fort, Aceh, Indonesia - Nazli Ismail; Muhammad Yanis; Amir Asyqari (Geosciences Journal, 2023)

Phenolic content of Terminalia catappa L. leaf and toxicity evaluation on red hybrid tilapia ( Oreochromis sp.) - Yahaya Yakubu; Muhammad T. Ahmad; Chou M. Chong; Intan S. Ismail; Khozirah Shaari (Journal of Fish Biology, 2023)
Despite the use of Terminalia catappa (TC) leaf by traditional fish farmers around the world to improve the health status of cultured fish, there is a paucity of information on comprehensive metabolite profile and the maximum safe dose of the plant. This study aims at profiling the methanol leaf extract of T. catappa, quantifying total phenolic content (TPC) as well as the total flavonoid content (TFC) and evaluating its acute toxicity on blood, plasma biochemical parameters and histopathology of some vital organs in red hybrid tilapia ( Oreochromis sp.). The experimental fish were acclimatised for 2 weeks and divided into six groups. Group (1) served as a control group and was administered 0.2 ml,g −1 of phosphate buffer saline (PBS). Groups 2–6 were orally administered T. catappa leaf extracts (0.2 ml.50 g −1 ) in the following sequence; 31.25, 62.5, 125, 250 and 500 mg.kg −1 body weight. The metabolites identified in T. catappa using liquid chromatography‐tandem mass electrospray ionisation spectrometry (LC‐ESI‐MS/MS) revealed the presence of organic acids, hydrolysable tannins, phenolic acids and flavonoids. Phenolic quantification revealed reasonable quantity of phenolic compounds (217.48 μg GAEmg −1 for TPC and 91.90 μg. QCEmg −1 for TFC). Furthermore, there was no significant difference in all the tested doses in terms of blood parameters and plasma biochemical analysis except for the packed cell volume (PCV) at 500 mg.kg −1 when compared to the control. Significant histopathological changes were observed in groups administered with the extract at 125, 250 and 500 mg.kg −1 doses. To a very large extent it is therefore safe to administer the extract at 31.25 and 62.5 mg.kg −1 in tilapia.

Fusarium falciforme and F. oxysporum causing postharvest fruit rot of watermelon (Citrullus lanatus) in Malaysia: A first report - Jagaathiswary Balasubramaniam; Ka Sheng Goh; Safia Fazariah Sani; Muhammad Waqar Alam; Nor Azliza Ismail; Mark L. Gleason; Hafizi Rosli (Crop Protection, 2023)

Immunomodulatory effects of Isochrysis galbana incorporated diet on Oreochromis sp. (red hybrid tilapia) via Sera-1H NMR metabolomics study - Muhammad Safwan Ahamad Bustamam; Hamza Ahmed Pantami; Khozirah Shaari; Chong Chou Min; Ahmed Mediani; Intan Safinar Ismail (Fish & Shellfish Immunology, 2023)

Functionalized graphene oxide-zinc oxide hybrid material and its deployment for adsorptive removal of levofloxacin from aqueous media - Nimra Ismail; Muhammad Imran; Muhammad Ramzan; Ayesha Anwar; Ibrahim A. Alsafari; Muhammad Asgher; Hafiz M.N. Iqbal (Environmental Research, 2023)

Effect of Different Solubilization pH Values on the Functional Properties of Protein Spirulina platensis Isolated Through Acidic Precipitation - N. A. Kamaruding; N. A. Muhammad Daud; N. Ismail; S. Shaharuddin (Journal of Aquatic Food Product Technology, 2022)

Projection of Hot and Cold Extremes in the Amu River Basin of Central Asia using GCMs CMIP6 - Obaidullah Salehie; Tarmizi bin Ismail; Mohammed Magdy Hamed; Shamsuddin Shahid; Mohd Khairul Idlan Muhammad (Stochastic Environmental Research and Risk Assessment, 2022)

Mechanisms of β-adrenergic receptors agonists in mediating pro and anti-apoptotic pathways in hyperglycemic Müller cells - Sher Zaman Safi; Laiba Saeed; Humaira Shah; Zahina Latif; Abid Ali; Muhammad Imran; Nawshad Muhammad; Talha Bin Emran; Vetriselvan Subramaniyan; Ikram Shah Bin Ismail (Molecular Biology Reports, 2022)

Correction to: Awareness regarding COVID‑19 and its effects on mental health among pre‑professional health sciences students at King Saud bin Abdulaziz University for health sciences in Riyadh and Jeddah, Saudi Arabia - Zackary Alghamdy; Ashwaq Alshahrani; Ismail Memon; Aslam Khan; Muhammad Anwar Khan; Yazeed Alrayani; Fulwah Alfawzan; Syed Faisal Zaidi (Environmental Science and Pollution Research, 2022)

Awareness regarding COVID-19 and its effects on mental health among pre-professional health sciences students at King Saud bin Abdulaziz University for health sciences in Riyadh and Jeddah, Saudi Arabia - Zackary Alghamdy; Ashwaq Alshahrani; Ismail Memon; Aslam Khan; Muhammad Anwar Khan; Yazeed Alrayani; Fulwah Alfawzan; Syed Faisal Zaidi (Environmental Science and Pollution Research, 2022)

Side-Scan Sonar Coupled with Scuba Diving Observation for Enhanced Monitoring of Benthic Artificial Reefs along the Coast of Terengganu, Peninsular Malaysia - Azizi Ali; Muhammad Ruzi Abdullah; Che Din Mohd Safuan; Aminudin Muhammad Afiq-Firdaus; Zainudin Bachok; Mohd Fadzil Mohd Akhir; Roslan Latif; Azri Muhamad; Tan Hock Seng; Adina Roslee; Khaira Ismail (Journal of Marine Science and Engineering, 2022)
Since the 1970s, artificial reef (AR) deployment has been one of the common approaches to augment the local production of coastal fish in Malaysia. However, there is a lack of strategy to assess and evaluate the success of pre-deployed AR. Realizing the need for an effective qualitative and quantitative monitoring and evaluation of AR, this study proposes side-scan sonar coupled with scuba diving observation for the enhanced monitoring of pre-deployed Bioceramic Korean (BK) AR along the coast of Terengganu, Peninsular Malaysia. This method employs an integrated side-scan sonar with a data acquisition system for the detection of the precise location of the BK AR which were deployed at Tukun Telaga Batin off the Terengganu coastline in 2003 by the Fisheries Development Authority of Malaysia (FDAM). Following the determination of the exact location of three BK AR areas, a scuba diving team was sent to survey the physical conditions of the AR and assess the feasibility of the AR as an artificial habitat for marine life. The scan sonar images were compared with the captured photographs and videos acquired during the scuba diving session for a comprehensive value-added assessment. The collected data from the scuba diving session were also processed to measure the fish diversity, the fish biomass, and identify the fish community surrounding the AR. Based on the results, the BK AR remained in extremely good condition, physically intact, without significant breakage or damage, and with no major subsidence into the sediment after 19 years of deployment. A total of 108 BK AR modules were detected in three large groups using the mosaicked sonar images. Following cross-examination to validate the AR measurements using the AR’s shadows on the seafloor, the height of the BK AR consistently ranged from 1.7 m to 1.8 m. In addition, 34 species of fish from 14 families and 26 genera were identified, with most species classified as reef-associated (RA) fish with a biomass value of 1173.31 ± 1136.69 kg m−3, indicating the successfulness of the BK AR as fish-aggregating devices (FADs). The growth of hard corals on top of the bioceramic plate of the AR module further supported the diversified community of marine life surrounding the BK AR. In conclusion, the side-scan sonar coupled with scuba diving observation demonstrates an effective qualitative and quantitative technique for the monitoring and evaluation of pre-deployed AR. This strategy is recommended to be utilized to determine the success of pre-deployment AR.

Biotechnological interventions in food waste treatment for obtaining value-added compounds to combat pollution - Aparna Ganapathy Vilasam Sreekala; Muhammad Heikal Bin Ismail; Vinod Kumar Nathan (Environmental Science and Pollution Research, 2022)

Early summer surface air temperature variability over Pakistan and the role of El Niño–Southern Oscillation teleconnections - Irfan Ur Rashid; Muhammad Adnan Abid; Mansour Almazroui; Fred Kucharski; Muhammad Hanif; Shaukat Ali; Muhammad Ismail (International Journal of Climatology, 2022)
Early summer (May–June) is the season where the surface air temperature (SAT) variability is largest and may result in extreme temperature conditions over Pakistan. Therefore, we analysed the early summer interannual SAT variability over Pakistan for the period 1981–2018 using observational dataset and model simulations. We noted that upper‐level anticyclonic circulation anomalies over Pakistan, which are associated with upper to the middle tropospheric descending motion, favour clear skies with an increase in net shortwave radiation that leads to extreme surface warming over the region. Moreover, the El Niño–Southern Oscillation (ENSO) based on Niño3.4 SST index is negatively associated with SAT anomalies over Pakistan. The cold ENSO phase favours the positive geopotential height anomalies due to the strengthening of the Walker circulation that enhance the sinking motion and result in less cloudiness leading to the extreme higher surface temperature conditions over Pakistan, while the opposite happens in the warm ENSO phase. Moreover, the Saudi‐KAU Atmospheric Global Climate Model (AGCM) simulated large‐scale patterns that are in good agreement with the observations. Sensitivity experiments with the AGCM confirm that cold SST anomalies in the ENSO region significantly favour above‐normal SAT anomalies over Pakistan, while the opposite happens in the warm ENSO phase. These results are important to understand and potentially predict regional heatwaves over the South Asian region, particularly over Pakistan.

Antidiarrheal and antispasmodic activities of Trillium govanianum rhizomes extract: involvement of calcium channel blockade - Naveed Muhammad; Shafiq Ur Rahman; Hilal Uddin; Omer Shehzad; Muhammad Ismail; Niaz Ali; Aslam Khan; Muhammad Shahid; Abid Ullah; Shujaat Ahmad; Haya Hussain; Ikram ul Haq; et al. (Natural Product Research, 2022)

Design considerations of variable rate liquid fertilizer applicator for mature oil palm trees - Muhammad Yamin; Wan Ishak bin Wan Ismail; Samsuzana Abd Aziz; Muhamad Saufi bin Mohd Kassim; Farah Naz Akbar; Muhammad Ibrahim (Precision Agriculture, 2022)

Cowpea induced physicochemical and biological rhizosphere changes in hydrocarbon contaminated soil - A. A. Farouq; H. Y. Ismail; A. B. Rabah; A. B. Muhammad; U. B. Ibrahim; A. Y. Fardami (Plant and Soil, 2022)

A comparative analysis of pre- and post-industrial spatiotemporal drought trends and patterns of Tibet Plateau using Sen slope estimator and steady-state probabilities of Markov Chain - Zhenya Li; Zulfiqar Ali; Tong Cui; Sadia Qamar; Muhammad Ismail; Amna Nazeer; Muhammad Faisal (Natural Hazards, 2022)

Anti-inflammatory and antioxidant activities of chemical constituents from the flower buds of Buddleja officinalis - Fei-Bing Huang; Na Liang; Nusrat Hussain; Xu-Dong Zhou; Muhammad Ismail; Qing-Ling Xie; Huang-He Yu; Yu-Qing Jian; Cai-Yun Peng; Bin Li; Bin Liu; Sheng-Huang Chen; et al. (Natural Product Research, 2022)

Use of Eudragit RS PO, HPMC K100M, Ethyl Cellulose, and Their Combination for Controlling Nicorandil Release from the Bilayer Tablets with Atorvastatin as an Immediate-Release Layer - Wajiha Iffat; Muhammad Harris Shoaib; Rabia Ismail Yousuf; Faaiza Qazi; Zafar Alam Mahmood; Iyad Naeem Muhammad; Kamran Ahmed; Farrukh Rafiq Ahmed; Muhammad Suleman Imtiaz (Journal of Pharmaceutical Innovation, 2022)

Preparation and evaluation of a coated smectite clay-based material modified with epichlorohydrin-dimethylamine for the diclofenac removal - Muhamad Sharafee Shamsudin; Muhammad Haziq Abdul Taib; Syahida Farhan Azha; Adrian Bonilla-Petriciolet; Suzylawati Ismail (Environmental Science and Pollution Research, 2022)

Controlling of Xanthomonas axonopodis pv. phaseoli by induction of phenolic compounds in bean plants using salicylic and benzoic acids - Kamal A. M. Abo-Elyousr; Muhammad Imran; Najeeb M. Almasoudi; Esmat F. Ali; Sabry Hassan; Nashwa M A. Sallam; Khamis Youssef; Ismail R. Abdel-Rahim; Hadeel M.M. Khalil Bagy (Journal of Plant Pathology, 2022)

Shallow Structure Fault and Fracture Mapping in Jaboi Volcano, Indonesia, Using VLF–EM and Electrical Resistivity Methods - Muhammad Yanis; Nazli Ismail; Faisal Abdullah (Natural Resources Research, 2022)

Metabolite profile and gene expression of the roots of oil palm seedlings treated with Hendersonia GanoEF1 and infected with Ganoderma boninense - Muhammad Faiz Ismail; Rosimah Nulit; Idris Abu Seman; Mohd Hafiz Ibrahim; Nurrashyeda Ramli (Journal of Plant Pathology, 2022)

Establishing a corporate social responsibility implementation model for promoting sustainability in the food sector: a hybrid approach of expert mining and ISM–MICMAC - Muhammad Shahjahan Usmani; Jianling Wang; Naveed Ahmad; Zia Ullah; Muzaffar Iqbal; Muhammad Ismail (Environmental Science and Pollution Research, 2022)

Hypercholesterolemia and 27-Hydroxycholesterol Increase S100A8 and RAGE Expression in the Brain: a Link Between Cholesterol, Alarmins, and Neurodegeneration - Raúl Loera-Valencia; Muhammad-Al-Mustafa Ismail; Julen Goikolea; Maria Lodeiro; Laura Mateos; Ingemar Björkhem; Elena Puerta; Mariana A. Romão; Cláudio M. Gomes; Paula Merino-Serrais; Silvia Maioli; Angel Cedazo-Minguez (Molecular Neurobiology, 2021)
Alterations in cholesterol metabolism in the brain have a major role in the physiology of Alzheimer’s disease (AD). Oxysterols are cholesterol metabolites with multiple implications in memory functions and in neurodegeneration. Previous studies have shown detrimental effects of cholesterol metabolites in neurons, but its effect in glial cells is unknown. We used a high-fat/high-cholesterol diet in mice to study the effects of hypercholesterolemia over the alarmin S100A8 cascade in the hippocampus. Using CYP27Tg, a transgenic mouse model, we show that the hypercholesterolemia influence on the brain is mediated by the excess of 27-hydroxycholesterol (27-OH), a cholesterol metabolite. We also employed an acute model of 27-OH intraventricular injection in the brain to study RAGE and S100A8 response. We used primary cultures of neurons and astrocytes to study the effect of high levels of 27-OH over the S100A8 alarmin cascade. We report that a high-fat/high-cholesterol diet leads to an increase in S100A8 production in the brain. In CYP27Tg, we report an increase of S100A8 and its receptor RAGE in the hippocampus under elevated 27-OH in the brain. Using siRNA, we found that 27-OH upregulation of RAGE in astrocytes and neurons is mediated by the nuclear receptor RXRγ. Silencing RXRγ in neurons prevented 27-OH-mediated upregulation of RAGE. These results show that S100A8 alarmin and RAGE respond to high levels of 27-OH in the brain in both neurons and astrocytes through RXRγ. Our study supports the notion that 27-OH mediates detrimental effects of hypercholesterolemia to the brain via alarmin signaling.

Functional identification of G. hirsutum genes for their role in normal plant development and resistance against Verticillium dahliae using virus-induced gene silencing - Roma Mustafa; Muhammad Javed Iqbal; Muhammad Hamza; Atiq Ur Rehman; Ismail Buzdar; Hira Kamal; Shahid Mansoor; Imran Amin (European Journal of Plant Pathology, 2021)

An analysis on the effect of coronavirus (COVID-19) pandemic movement control order (MCOS) on the solid waste generation in Peninsular Malaysia - Muhammad Afiq Brohan; Nazri Che Dom; Ahmad Razali Ishak; Samsuri Abdullah; Hasber Salim; Sharifah Norkhadijah Syed Ismail; Nopadol Precha (Environmental Science and Pollution Research, 2021)

Arsenic exposure through drinking groundwater and consuming wastewater-irrigated vegetables in Multan, Pakistan - Mamoona Amir; Salman Asghar; Muhammad Ahsin; Shahid Hussain; Amir Ismail; Muhammad Riaz; Safina Naz (Environmental Geochemistry and Health, 2021)

Seasonal predictability of Ethiopian Kiremt rainfall and forecast skill of ECMWF's SEAS5 model - Muhammad Azhar Ehsan; Michael K. Tippett; Andrew W. Robertson; Mansour Almazroui; Muhammad Ismail; Tufa Dinku; Nachiketa Acharya; Asher Siebert; Jemal Seid Ahmed; Asaminew Teshome (Climate Dynamics, 2021)

Geospatial analysis of desertification vulnerability using Mediterranean desertification and land use (MEDALUS) model in Kebbi State, Nigeria - Muhammad Mansur Aliero; Mohd Hasmadi Ismail; Mohamad Azani Alias; Alias Mohd Sood (Applied Geomatics, 2021)

Reduced root mycorrhizal colonization as affected by phosphorus fertilization is responsible for high cadmium accumulation in wheat - M. Atilla Yazici; Muhammad Asif; Yusuf Tutus; Ibrahim Ortas; Levent Ozturk; Hans Lambers; Ismail Cakmak (Plant and Soil, 2021)

Survey of antibodies to Rift Valley fever virus and associated risk factors in one-humped camels (Camelus dromedarius) slaughtered in Maiduguri abattoir, Borno State, Nigeria - Hassan Ismail Musa; Caleb Ayuba Kudi; Muhammad Mamman Gashua; Abubakar Sadiq Muhammad; Abdulyeken Olawale Tijjani; Adamu Saleh Saidu; Sani Mohammed; Saleh Mohammed Jajere; Shuaibu Gidado Adamu (Tropical Animal Health and Production, 2021)

Genome-wide diversity and structure variation among lablab [Lablab purpureus (L.) Sweet] accessions and their implication in a Forage breeding program - Julius Pyton Sserumaga; Siraj Ismail Kayondo; Abasi Kigozi; Muhammad Kiggundu; Clementine Namazzi; Kato Walusimbi; James Bugeza; Allen Molly; Swidiq Mugerwa (Genetic Resources and Crop Evolution, 2021)
Most orphan crops have not been fully sequenced, hence we rely on genome sequences of related species to align markers to different chromosomes. This hinders their utilisation in plant population improvement programs. Utilising the advances in the science of sequencing technologies, the population structure, relatedness, and genetic diversity among accessions can be assessed quickly for better exploitation in forage breeding programs. Using DArTseq technology, we studied the genetic and structural variation in 65 Lablab purpureus (L.) Sweet conserved gene-bank accessions using 9320 DArTseq-based SNPs and 15,719 SilicoDart markers. These markers had a low discriminating ability with mean polymorphic information content (P.I.C.) of 0.14 with DArTseq-based SNPs and 0.13 with SilicoDart markers. However, the markers had a high mean call rate of 73% with DArTseq-based SNPs and 97% with SilicoDart markers. Analysis of molecular variance revealed a high within populations variance (99.4%), indicating a high gene exchange or low genetic differentiation (PhiPT = 0.0057) among the populations. Structure analysis showed three allelic pools in variable clusters of ΔK = 3 and 6. Phylogenetic tree of lablab accessions showed three main groups with variable membership coefficients. Most pairs of accessions (40.3%) had genetic distances between 0.10 and 0.15 for SilicoDart markers, while for DArTseq-based SNPs, (46.5%) had genetic distances between 0.20 and 0.25. Phylogenetic clustering and minimum spanning analysis divided the 65 accessions into three groups, irrespective of their origin. For the first time, this study produced high-density markers with good genom coverage. The utilisation of these accessions in a forage program will base on the information from molecular-based grouping. The outcomes uncovered the presence of noteworthy measure of variety in Uganda, CIAT and ILRI accessions, thus demonstrating an opportunity for further marker-trait-association studies.

Correction to: Does globalization affect the green economy and environment? The relationship between energy consumption, carbon dioxide emissions, and economic growth - Muhammad Khalid Anser; Muhammad Usman; Danish Iqbal Godil; Malik Shahzad Shabbir; Arshian Sharif; Mosab Ismail Tabash; Lydia Bares Lopez (Environmental Science and Pollution Research, 2021)

Cyclodextrin Complex Formation with Water-Soluble Drugs: Conclusions from Isothermal Titration Calorimetry and Molecular Modeling - Karim S. Shalaby; Muhammad I. Ismail; Alf Lamprecht (AAPS PharmSciTech, 2021)
Cyclodextrin (CD) complexes are frequently used for enhancing the solubility or absorption of poorly water-soluble drugs. On the contrary, little is known about their complex formation with water-soluble drugs. Here, we have studied the interaction between 2-hydroxypropyl β-CD (HPβCD) and three water-soluble drugs, namely naloxone (NX), oxycodone (OC), and tramadol (TR), by isothermal titration calorimetry (ITC) combined with molecular modeling in view of the potential impact on drug release. The results showed that the complex formation of HPβCD with all three drugs occurs spontaneously. The complexes formed with NX and OC were found to be 2NX:1HPβCD and 3OC:2HPβCD, respectively. TR was found to form 2 complexes with HPβCD; of 1:2 and 1:1 complexation ratios. The binding of HPβCD to NX was greater than to OC due to the higher hydrophobicity of the structure of the former. Moreover, the binding affinity of HPβCD to TR was higher than to OC, which indicated the effect of the higher flexibility of the guest in increasing the binding affinity. In vitro drug release experiments from the various complexes revealed a significant impact of the stoichiometry of the complex on the release profiles. Accordingly, the co-administration of cyclodextrins with water-soluble drugs should be closely monitored, as it may result in unintentional complex formation that can potentially impact the drugs’ gastrointestinal absorption.

Acetylcholinesterase and α-glucosidase inhibitory compounds from Callicarpa maingayi - Muhammad A. Ado; M. Maulidiani; Intan Safinar Ismail; Hasanah M. Ghazali; Khozirah Shaari; Faridah Abas (Natural Product Research, 2021)

Geotechnical characterization of bentonite-fly ash mixtures for their application as landfill liner in Pakistan - Hafiz Muhammad Awais Rashid; Arsalan Sardar; Atif Ismail (Arabian Journal of Geosciences, 2021)

The northernmost part of the Great Sumatran Fault map and images derived from gravity anomaly - Muhammad Yanis; Faisal Abdullah; Nasrullah Zaini; Nazli Ismail (Acta Geophysica, 2021)

The development of evolutionary computing model for simulating reference evapotranspiration over Peninsular Malaysia - Mohd Khairul Idlan Muhammad; Shamsuddin Shahid; Tarmizi Ismail; Sobri Harun; Ozgur Kisi; Zaher Mundher Yaseen (Theoretical and Applied Climatology, 2021)

Differences in uptake and translocation of foliar‐applied Zn in maize and wheat - Raheela Rehman; Muhammad Asif; Ismail Cakmak; Levent Ozturk (Plant and Soil, 2021)

Asp-376-Glu substitution endows target-site resistance to AHAS inhibitors in Limnocharis flava, an invasive weed in tropical rice fields - Norazua Zakaria; Rabiatuladawiyah Ruzmi; Salmah Moosa; Norhayu Asib; Dzarifah Zulperi; Siti Izera Ismail; Muhammad Saiful Ahmad-Hamdani (Physiology and Molecular Biology of Plants, 2021)

Synthesis, β-glucuronidase inhibition and molecular docking studies of cyano-substituted bisindole hydrazone hybrids - Obaidurahman Abid; Syahrul Imran; Muhammad Taha; Nor Hadiani Ismail; Waqas Jamil; Syed Muhammad Kashif; Khalid Mohammed Khan; Juliana Yusoff (Molecular Diversity, 2021)

RETRACTED ARTICLE: Protective effect of myricetin on nonylphenol-induced testicular toxicity: biochemical, steroidogenic, hormonal, spermatogenic, and histological-based evidences - Muhammad Umar Ijaz; Haseeb Anwar; Shabnoor Iqbal; Hammad Ismail; Asma Ashraf; Shama Mustafa; Abdul Samad (Environmental Science and Pollution Research, 2021)

Spatiotemporal variability of multifractal properties of fineresolution daily gridded rainfall fields over India - Adarsh Sankaran; Sagar Rohidas Chavan; Mumtaz Ali; Archana Devarajan Sindhu; Drisya Sasi Dharan; Muhammad Ismail Khan (Natural Hazards, 2021)

Arsenic and lead in the indoor residential settings of different socio-economic status; assessment of human health risk via dust exposure - Nadeem Ali; Syed Ali Musstjab Akber Shah Eqani; Ehtisham Nazar; Nabil A. Alhakamy; Muhammad Imtiaz Rashid; Khurram Shahzad; Jahan Zeb; Heqing Shen; Iqbal Mohammad Ibrahim Ismail; Hussain Mohammed Salem Ali Albar (Environmental Science and Pollution Research, 2021)

Emission factors of some common grass species in West Africa - Khadijat Abdulkareem Abdulraheem; Jamiu Adetayo Adeniran; Adeniyi Saheed Aremu; Muhammad-Najeeb O. Yusuf; Jeleel Adekunle Adebisi; Nusirat Aderinsola Sadiku; Oluwatosin Onaopemipo Olofintoye; Abubakar Ismail; Jacob Ademola Sonibare (Environmental Monitoring and Assessment, 2020)

Comparison of two model calibration approaches and their influence on future projections under climate change in the Upper Indus Basin - Muhammad Fraz Ismail; Bibi S. Naz; Michel Wortmann; Markus Disse; Laura C. Bowling; Wolfgang Bogacki (Climatic Change, 2020)
This study performs a comparison of two model calibration/validation approaches and their influence on future hydrological projections under climate change by employing two climate scenarios (RCP2.6 and 8.5) projected by four global climate models. Two hydrological models (HMs), snowmelt runoff model + glaciers and variable infiltration capacity model coupled with a glacier model, were used to simulate streamflow in the highly snow and glacier melt–driven Upper Indus Basin. In the first (conventional) calibration approach, the models were calibrated only at the basin outlet, while in the second (enhanced) approach intermediate gauges, different climate conditions and glacier mass balance were considered. Using the conventional and enhanced calibration approaches, the monthly Nash-Sutcliffe Efficiency (NSE) for both HMs ranged from 0.71 to 0.93 and 0.79 to 0.90 in the calibration, while 0.57–0.92 and 0.54–0.83 in the validation periods, respectively. For the future impact assessment, comparison of differences based on the two calibration/validation methods at the annual scale (i.e. 2011–2099) shows small to moderate differences of up to 10%, whereas differences at the monthly scale reached up to 19% in the cold months (i.e. October–March) for the far future period. Comparison of sources of uncertainty using analysis of variance showed that the contribution of HM parameter uncertainty to the overall uncertainty is becoming very small by the end of the century using the enhanced approach. This indicates that enhanced approach could potentially help to reduce uncertainties in the hydrological projections when compared to the conventional calibration approach.

Predicting peak summer monsoon precipitation over Pakistan in ECMWF SEAS5 and North American Multimodel Ensemble - Muhammad Azhar Ehsan; Michael K. Tippett; Fred Kucharski; Mansour Almazroui; Muhammad Ismail (International Journal of Climatology, 2020)
The potential and actual forecast skill of peak summer monsoon precipitation (July–August [JA]) over the core summer monsoon region of Pakistan (CSMRP: 68°–76°E, 30°–36°N) is investigated. The predictions from the latest version of the European Centre for Medium‐Range Weather Forecast System5 (SEAS5) and the North American Multimodel Ensemble (NMME) initialized in the beginning of June, May, and April are utilized. The potential skill is estimated by signal‐to‐noise ratio and perfect model correlation. The forecast skill is evaluated using the temporal anomaly correlation as well as the ranked probability skill score for probabilistic forecasts. The SEAS5 generally captures the observed climatological mean and variability patterns of peak summer monsoon precipitation over the region, with some biases mainly located over the complex topography zones. Observed SST anomalies in the El Niño–Southern Oscillation (ENSO) region are negatively correlated with observed peak summer monsoon precipitation over the region. The ENSO–precipitation connection is weakly reproduced in SEAS5 at Lead‐1 and fades gradually with increasing lead time. The potentially predictable component (signal) is small compared to the unpredictable part (noise). Nonetheless, statistically significant potential skill is found over the CSMRP. However, the forecast skill of peak summer monsoon precipitation over the region is lower than the potential skill in SEAS5. A multimodel ensemble average of five models shows little benefit in predicting peak monsoon precipitation over Pakistan. Extended spatial averaging has some impact on the skill; however, temporal averaging has no effect on the skill of the summer monsoon precipitation in SEAS5. Together these results show limitations of the current seasonal prediction models and demonstrate their inadequate performance in predicting peak summer monsoon precipitation over Pakistan.

Identification of Edible Fish Species of Pakistan Through DNA Barcoding - Muhammad Zubair Ghouri; Muhammad Ismail; Muhammad Asif Javed; Sultan Habibullah Khan; Nayla Munawar; Abdullah Bin Umar; Mehr-un-Nisa; Syed Ovais Aftab; Shazia Amin; Zulqurnain Khan; Aftab Ahmad (Frontiers in Marine Science, 2020)

Telomerase reverse transcriptase downregulation by RNA interference modulates endoplasmic reticulum stress and mitochondrial energy production - Muhammad Zuhair Mohd Zain; Nor Hayati Ismail; Nadhirah Ahmad; Sarina Sulong; Saiful Anuar Karsani; Nazia Abdul Majid (Molecular Biology Reports, 2020)

Predictive analysis of CO2 emissions and the role of environmental technology, energy use and economic output: evidence from emerging economies - Sidrah Ahmed; Khalid Ahmed; Muhammad Ismail (Air Quality, Atmosphere & Health, 2020)

A novel approach for high-level expression and purification of GST-fused highly thermostable Taq DNA polymerase in Escherichia coli - Rahman Ud Din; Muhammad Ismail Khan; Asad Jan; Shah Anwar Khan; Irshad Ali (Archives of Microbiology, 2020)

Enteric methane emissions of grazing short-horn zebu weaner bulls vary with estimation method and level of crude protein supplementation - Muhammad Kiggundu; Ziwena Nantongo; Siraj Ismail Kayondo; Swidiq Mugerwa (Tropical Animal Health and Production, 2020)

Assessment of denitrification potential for coastal and inland sites using groundwater and soil analysis: the multivariate approach - Muntaka Dahiru; Nor Kartini Abu Bakar; Ismail Yus off; Kah Hin Low; Muhammad N. Mohd (Environmental Monitoring and Assessment, 2020)

Comparative adsorption capabilities of rubbish tissue paper–derived carbon-doped MgO and CaCO3 for EBT and U(VI), studied by batch, spectroscopy and DFT calculations - Ayub Khan; Dongli Wei; Fazli Khuda; Ran Ma; Muhammad Ismail; Yuejie Ai (Environmental Science and Pollution Research, 2020)

Diverse and dynamic roles of F-box proteins in plant biology - Nur-Athirah Abd-Hamid; Muhammad-Izzat Ahmad-Fauzi; Zamri Zainal; Ismanizan Ismail (Planta, 2020)

TiO2 Coated-Asphalt Buton Photocatalyst for High-Performance Motor Vehicles Gas Emission Mitigation - Muhammad Zakir Muzakkar; Muhammad Nurdin; Ima Ismail; Maulidiyah Maulidiyah; Dwiprayogo Wibowo; Ratna Ratna; Siti Khatijah Md Saad; Akrajas Ali Umar (Emission Control Science and Technology, 2020)

Molecular characterization and phylogenetic analysis of Pantoea stewartii subspecies stewartii causing bronzing disease of jackfruit in Malaysia based on cps and hrp gene sequences - Rohaya Ibrahim; Noor Wahida Ismail-Suhaimy; Tan Shu-Qing; Siti Izera Ismail; Nuraizat Abidin; Mansor Hakiman; Daljit Singh Karam; Muhammad Saiful Ahmad-Hamdani; Mohd Termizi Yusof; Dzarifah Zulperi (Journal of Plant Pathology, 2020)

Synthesis, α-amylase inhibition and molecular docking study of bisindolylmethane sulfonamide derivatives - Muhammad Taha; Tayyaba Noreen; Syahrul Imran; Fasial Nawaz; Sridevi Chigurupati; Manikandan Selvaraj; Fazal Rahim; Nor Hadiani Ismail; Ashok Kumar; Ashik Mosaddik; Abdullah M. Alghamdi; Yousif Abdulrahman nasser alqahtani; et al. (Medicinal Chemistry Research, 2019)

Selection of CMIP5 multi-model ensemble for the projection of spatial and temporal variability of rainfall in peninsular Malaysia - Muhammad Noor; Tarmizi bin Ismail; Shamsuddin Shahid; Kamal Ahmed; Eun-Sung Chung; Nadeem Nawaz (Theoretical and Applied Climatology, 2019)

Potential predictability of Arabian peninsula summer surface air temperature in the North American multimodel ensemble - Muhammad Azhar Ehsan; Fred Kucharski; Mansour Almazroui; Muhammad Ismail; Michael K. Tippett (Climate Dynamics, 2019)

Hydrous ferric oxide nanoparticles hosted porous polyethersulfone adsorptive membrane: chromium (VI) adsorptive studies and its applicability for water/wastewater treatment - Norfadhilatuladha Abdullah; Norhaniza Yusof; Muhammad Hafiz Abu Shah; Syarifah Nazirah Wan Ikhsan; Zhi-Chien Ng; Subrata Maji; Woei Jye Lau; Juhana Jaafar; Ahmad Fauzi Ismail; Katsuhiko Ariga (Environmental Science and Pollution Research, 2019)

Social implications of palm oil production through social life cycle perspectives in Johor, Malaysia - Khairul Izzuddin Muhammad; Amir Hamzah Sharaai; Mohd Mansor Ismail; Rosta Harun; Wong Siew Yien (The International Journal of Life Cycle Assessment, 2019)

Identifying a Gene Knockout Strategy Using a Hybrid of Simple Constrained Artificial Bee Colony Algorithm and Flux Balance Analysis to Enhance the Production of Succinate and Lactate in Escherichia Coli - Mei Kie Hon; Mohd Saberi Mohamad; Abdul Hakim Mohamed Salleh; Yee Wen Choon; Kauthar Mohd Daud; Muhammad Akmal Remli; Mohd Arfian Ismail; Sigeru Omatu; Richard O. Sinnott; Juan Manuel Corchado (Interdisciplinary Sciences: Computational Life Sciences, 2019)

Earthworms as plug flow reactors: a first-order kinetic study on the gut of the vermicomposting earthworm Eudrilus eugeniae - Katheem Kiyasudeen; Mahamad Hakimi Ibrahim; Syahidah Akmal Muhammad; Sultan Ahmed Ismail; Fadzil Noor Gonawan; Mark Harris Zuknik (Environmental Science and Pollution Research, 2018)

Assessment of field evolved resistance to some broad-spectrum insecticides in cotton jassid, Amrasca devastans from southern Punjab, Pakistan - Nasir Abbas; Muhammad Ismail; Masood Ejaz; Iqra Asghar; Aima Irum; Sarfraz Ali Shad; Muhammad Binyameen (Phytoparasitica, 2018)

Trends and variations in the prescribing of secondary preventative cardiovascular therapies for non-ST elevation myocardial infarction (NSTEMI) in Malaysia - Padmaa Venkatason; Nur Lisa Zaharan; Muhammad Dzafir Ismail; Wan Azman Wan Ahmad; Ahmad Syadi Mahmood Zuhdi (European Journal of Clinical Pharmacology, 2018)

Whole-exome sequencing analysis reveals co-segregation of a COL20A1 missense mutation in a Pakistani family with striate palmoplantar keratoderma - Muhammad Ismail Khan; Soyeon Choi; Muhammad Zahid; Habib Ahmad; Roshan Ali; Musharraf Jelani; Changsoo Kang (Genes & Genomics, 2018)

Sensitivity to house dust mite allergens and prevalence of allergy-causing house dust mite species in Pothwar, Pakistan - Rubaba Hamid Shafique; Shamim Akhter; Shahid Abbas; Muhammad Ismail (Experimental and Applied Acarology, 2018)

Suppression of PGE2 production via disruption of MAPK phosphorylation by unsymmetrical dicarbonyl curcumin derivatives - Mohd Fadhlizil Fasihi Mohd Aluwi; Kamal Rullah; Md. Areeful Haque; Bohari M. Yamin; Waqas Ahmad; Muhammad Wahab Amjad; Sze Wei Leong; Nurul Amira Fahmizar; Juriyati Jalil; Faridah Abas; Nor Hadiani Ismail; Ibrahim Jantan; et al. (Medicinal Chemistry Research, 2017)

Bacillus safensis with plant-derived smoke stimulates rice growth under saline conditions - Muhammad Hafeez Ullah Khan; Jabar Zaman Khan Khattak; Muhammad Jamil; Ijaz Malook; Shahid Ullah Khan; Mehmood Jan; Ismail Din; Shah Saud; Muhammad Kamran; Hesham Alharby; Shah Fahad (Environmental Science and Pollution Research, 2017)

Comparative studies of three novel freshwater microalgae strains for synthesis of silver nanoparticles: insights of characterization, antibacterial, cytotoxicity and antiviral activities - Muneeba Khalid; Nauman Khalid; Iftikhar Ahmed; Rumeza Hanif; Muhammad Ismail; Hussnain Ahmed Janjua (Journal of Applied Phycology, 2017)

Currently used organophosphate and brominated flame retardants in the environment of China and other developing countries (2000–2016) - Nadeem Ali; Khurram Shahzad; Muhammad Imtiaz Rashid; Heqing Shen; Iqbal Mohammad Ibrahim Ismail; Syed Ali Musstjab Akber Shah Eqani (Environmental Science and Pollution Research, 2017)

Synthesis of 2-phenyl-1H-imidazo[4,5-b]pyridine as type 2 diabetes inhibitors and molecular docking studies - Muhammad Taha; Nor Hadiani Ismail; Syahrul Imran; Izzatul Ainaa; Manikandan Selvaraj; Mohd syukri baharudin; Muhammad Ali; Khalid Mohammed Khan; Nizam Uddin (Medicinal Chemistry Research, 2017)

Skill and predictability in multimodel ensemble forecasts for Northern Hemisphere regions with dominant winter precipitation - Muhammad Azhar Ehsan; Michael K. Tippett; Mansour Almazroui; Muhammad Ismail; Ahmed Yousef; Fred Kucharski; Mohamed Omar; Mahmoud Hussein; Abdulrahman A. Alkhalaf (Climate Dynamics, 2017)

Health assessment using aqua-quality indicators of alpine streams (Khunjerab National Park), Gilgit, Pakistan - Salar Ali; Junfeng Gao; Farida Begum; Atta Rasool; Muhammad Ismail; Yongjiu Cai; Shaukat Ali; Shujaat Ali (Environmental Science and Pollution Research, 2017)

Comparative enzyme inhibition study of 1-deazapurines - Iftikhar Ali; Ajmal Khan; Amjad Hussain; Umar Farooq; Muhammad Ismail; Viqar Hyder; Viqar U. Ahmad; Viktor O. Iaroshenko; Hidayat Hussain; Peter Langer (Medicinal Chemistry Research, 2016)

Syntheses, in vitro evaluation and molecular docking studies of 5-bromo-2-aryl benzimidazoles as α-glucosidase inhibitors - Tanzila Arshad; Khalid Mohammed Khan; Najma Rasool; Uzma Salar; Shafqat Hussain; Tehreem Tahir; Mohammed Ashraf; Abdul Wadood; Muhammad Riaz; Shahnaz Perveen; Muhammad Taha; Nor Hadiani Ismail (Medicinal Chemistry Research, 2016)

New lipoxygenase and cholinesterase inhibitory sphingolipids from Carthamus oxyacantha - Muhammad Dilshad; Naheed Riaz; Muhammad Saleem; Nusrat Shafiq; Muhammad Ashraf; Tayaba Ismail; Hafiza Mehwish Rafiq; Abdul Jabbar (Natural Product Research, 2016)

RETRACTED ARTICLE: Floristic and ethnoecological diversity in various habitats of a semi-arid area in the Chakwal district (Pakistan), with special emphasis on medicinal plants - Mehwish Jamil Noor; Mushtaq Ahmad; Muhammad Zafar; Maliha Sarfraz; Ismail Yusoff; Yatimah Alias; Muhammad Aqeel Ashraf (Plant Ecology, 2016)

In vitro propagation and cardenolide profiling of Digitalis ferruginea subsp. schischkinii, a medicinally important foxglove species with limited distribution in Northern Turkey - Buhara Yücesan; Aliyu Mohammed; İsmail Eker; Muhammad Sameeullah; Öznur Demir-Ordu; Cansu Cihangir; Nevin Şahbaz; Özge Kaya; Frieder Müller-Uri; Wolfgang Kreis; Ekrem Gürel (In Vitro Cellular & Developmental Biology - Plant, 2016)

Chaetomium endophytes: a repository of pharmacologically active metabolites - Nighat Fatima; Syed Aun Muhammad; Ibrar Khan; Muneer Ahmed Qazi; Irum Shahzadi; Amara Mumtaz; Muhammad Ali Hashmi; Abida Kalsoom Khan; Tariq Ismail (Acta Physiologiae Plantarum, 2016)

A novel antimicrobial flavonoid from the stem bark of Commiphora pedunculata (Kotschy & Peyr.) Engl. - Nasir Tajuddeen; Muhammad S. Sallau; Aliyu M. Musa; Sani M. Yahaya; James D. Habila; Abdullahi Musa Ismail (Natural Product Research, 2016)

Synthesis of 2-(2-methoxyphenyl)-5-phenyl-1,3,4-oxadiazole derivatives and evaluation of their antiglycation potential - Muhammad Taha; Nor Hadiani Ismail; Waqas Jamil; Syahrul Imran; Fazal Rahim; Syed Muhammad Kashif; Mohd Zulkefeli (Medicinal Chemistry Research, 2016)

Isolation and phylogenetic analysis of caprine Orf virus in Malaysia - Ashwaq Ahmed Abdullah; Muhammad Farid Bin Ismail; Krishnan Nair Balakrishnan; Jamilu Abubakar Bala; Homayoun Hani; Yusuf Abba; Mohd Kamaruddin Awang Isa; Faez Firdaus Jesse Abdullah; Siti Suri Arshad; Zeenatul Allaudin Nazariah; Rasedee Abdullah; Noordin Mohamed Mustapha; et al. (VirusDisease, 2015)

Estimated daily intake and health risk of heavy metals by consumption of milk - Amir Ismail; Muhammad Riaz; Saeed Akhtar; Tariq Ismail; Zulfiqar Ahmad; Muhammad Saad Hashmi (Food Additives & Contaminants Part B-Surveillance, 2015)

Neuroprotective effect from stem bark extracts of Knema laurina against H 2 O 2 - and Aβ 1–42 -induced cell death in human SH-SY5Y cells - Norsharina Ismail; Muhammad Nadeem Akhtar; Maznah Ismail; Seema Zareen; Syed Adnan Ali Shah; Nordin Hj Lajis; Saiful N. Tajuddin (Natural Product Research, 2015)

Synthesis and evaluation of unsymmetrical heterocyclic thioureas as potent β-glucuronidase inhibitors - Muhammad Taha; Nor Hadiani Ismail; Waqas Jamil; Khalid Mohammed Khan; Uzma Salar; Syed Muhammad Kashif; Fazal Rahim; Yawar Latif (Medicinal Chemistry Research, 2015)

Arsenic Adsorption Using Palm Oil Waste Clinker Sand Biotechnology: an Experimental and Optimization Approach - Muhammad Abdur Rehman; Ismail Yusoff; Rasel Ahmmad; Yatimah Alias (Water, Air, & Soil Pollution, 2015)

Erratum to: Synthesis crystal structure of 2-methoxybenzoylhydrazones and evaluation of their α-glucosidase and urease inhibition potential - Muhammad Taha; Nor Hadiani Ismail; Mohd Syukri Baharudin; Salima Lalani; Sadia Mehboob; Khalid Mohammed Khan; Sammer Yousuf; Salman Siddiqui; Fazal Rahim; M. Iqbal Choudhary (Medicinal Chemistry Research, 2015)

Synthesis crystal structure of 2-methoxybenzoylhydrazones and evaluation of their α-glucosidase and urease inhibition potential - Muhammad Taha; Nor Hadiani Ismail; Mohd Syukri Baharudin; Salima Lalani; Sadia Mehboob; Khalid M. Khan; Sammer yousuf; Salman Siddiqui; Fazal Rahim; M. Iqbal Choudhary (Medicinal Chemistry Research, 2015)

POM analyses of anti-kinase activity of thirteen peptide alkaloids extracted from Zizyphus species - Moulay H. Youssoufi; Taibi Ben Hadda; Ismail Warad; Muhammad Moazzam Naseer; Yahia Nasser Mabkhot; Ammar Bader (Medicinal Chemistry Research, 2015)

Synthesis of indole-2-hydrazones in search of potential leishmanicidal agents - Muhammad Taha; Nor Hadiani Ismail; Muhammad Ali; Khalid M. Khan; Waqas Jamil; Syed Muhammad Kashif; Mohammad Asraf (Medicinal Chemistry Research, 2014)

Permian ultrafelsic A-type granite from Besar Islands group, Johor, peninsular Malaysia - Azman A Ghani; Fatin Izzani Hazad; Azmiah Jamil; Quek Long Xiang; Wan Nur Atiqah Wan Ismail; Sun-Lin Chung; Yu-Ming Lai; Muhammad Hatta Roselee; Nur Islami; Kyaw Kyaw Nyein; Meor Hakif Amir Hassan; Mohd Farid Abu Bakar; et al. (Journal of Earth System Science, 2014)

Effect of Ascorbic Acid on the Degradation of Cyanocobalamin and Hydroxocobalamin in Aqueous Solution: A Kinetic Study - Iqbal Ahmad; Kiran Qadeer; Saima Zahid; Muhammad Ali Sheraz; Tehmina Ismail; Waqar Hussain; Izhar Ahmad Ansari (AAPS PharmSciTech, 2014)

Livelihood diversification as an adaptation approach to change in the pastoral Hindu-Kush Himalayan region - Ning Wu; Muhammad Ismail; Srijana Joshi; Shao-liang Yi; Ritu Meher Shrestha; Abdul Wahid Jasra (Journal of Mountain Science, 2014)

Cesium-137: Radio-Chemistry, Fate, and Transport, Remediation, and Future Concerns - Muhammad Aqeel Ashraf; Shatirah Akib; Mohd. Jamil Maah; Ismail Yusoff; Khaled S. Balkhair (Critical Reviews in Environmental Science and Technology, 2014)

Heavy metals in vegetables and respective soils irrigated by canal, municipal waste and tube well waters - Amir Ismail; Muhammad Riaz; Saeed Akhtar; Tariq Ismail; Mamoona Amir; Muhammad Zafar-ul-Hye (Food Additives & Contaminants Part B-Surveillance, 2014)

Study of contaminant transport at an open-tipping waste disposal site - Muhammad Aqeel Ashraf; Ismail Yusoff; Mohamad Yusof; Yatimah Alias (Environmental Science and Pollution Research, 2013)

Rapamycin Induces Apoptosis When Autophagy is Inhibited in T-47D Mammary Cells and Both Processes are Regulated by Phlda1 - Ahmed Ismail Hassan Moad; Tengku Sifzizul Tengku Muhammad; Chern Ein Oon; Mei Lan Tan (Cell Biochemistry and Biophysics, 2013)

Development of a Polygonum minus cell suspension culture system and analysis of secondary metabolites enhanced by elicitation - Muhammad Faizan A. Shukor; Ismanizan Ismail; Zamri Zainal; Normah Mohd Noor (Acta Physiologiae Plantarum, 2013)

Measurement of radionuclides and absorbed dose rates in soil samples of Peshawar, Pakistan, using gamma ray spectrometry - Hasan M. Khan; Muhammad Ismail; Muhammad Abid Zia; Khalid Khan (Isotopes in Environmental and Health Studies, 2012)

The ribosomal protein L19 mRNA is induced by copper exposure in the swordtail fish, Xiphophorus helleri - Dwinna Aliza; Chiew-Lian Tey; Ida Shazrina Ismail; Meng-Kiat Kuah; Alexander Chong Shu-Chien; Tengku Sifzizul Tengku Muhammad (Molecular Biology Reports, 2012)

Molecular marker assisted for recognition drought tolerant in some of bread wheat genotypes - Abdelaleim Ismail ElSayed; Muhammad Suhail Rafudeen (Journal of Crop Science and Biotechnology, 2012)

Effect of Zinc and Iron Fortification of the Feed on Liver and Thyroid Function in Rats - Saeed Akhtar; Faqir M. Anjum; Zia Ur Rehman; M. Riaz; Muhammad Arshad; Abdul Basit; Tariq Ismail (Biological Trace Element Research, 2011)

A mutant l-asparaginase II signal peptide improves the secretion of recombinant cyclodextrin glucanotransferase and the viability of Escherichia coli - Noor Faizah Ismail; Salehhuddin Hamdan; Nor Muhammad Mahadi; Abdul Munir Abdul Murad; Amir Rabu; Farah Diba Abu Bakar; Peter Klappa; Rosli Md. Illias (Biotechnology Letters, 2011)

Assessment of Radionuclides, Trace Metals and Radionuclide Transfer from Soil to Food of Jhangar Valley (Pakistan) Using Gamma-Ray Spectrometry - Hasan M. Khan; Zahid S. Chaudhry; Muhammad Ismail; Khalid Khan (Water, Air, & Soil Pollution, 2010)

Development and Evaluation of Hydrophilic Colloid Matrix of Famotidine Tablets - Muhammad Harris Shoaib; Saniah Al Sabah Siddiqi; Rabia Ismail Yousuf; Kamran Zaheer; Muhammad Hanif; Saeed Rehana; Sabahat Jabeen (AAPS PharmSciTech, 2010)

Programmed Cell Death Pathways and Current Antitumor Targets - Mei Lan Tan; Jer Ping Ooi; Nawfal Ismail; Ahmed Ismail Hassan Moad; Tengku Sifzizul Tengku Muhammad (Pharmaceutical Research, 2009)

Evaluation of the Acute Toxicity of Profenofos and Its Effects on the Behavioral Pattern of Fingerling Common Carp (Cyprinus carpio L., 1758) - Muhammad Ismail; Rahat Ali; Tayyaba Ali; Usman Waheed; Qaiser Mahmood Khan (Bulletin of Environmental Contamination and Toxicology, 2009)

Identification of Wap65, a human homologue of hemopexin as a copper-inducible gene in swordtail fish, Xiphophorus helleri - Dwinna Aliza; Ida Shazrina Ismail; Meng-Kiat Kuah; Alexander Chong Shu-Chien; Tengku Sifzizul Tengku Muhammad (Fish Physiology and Biochemistry, 2008)